A fumarate tablet of vorolanib and a preparation method and use thereof
Patent Information
- Application Number
- CN202410916545.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Existing vonoprazan fumarate tablets suffer from several problems, including difficulty in simultaneously achieving key quality attributes such as stability, disintegration or dissolution, tablet weight variation, uniformity, and bioequivalence. Furthermore, the preparation process is complex, costly, and inefficient.
Using specific formulations and preparation methods, including tablet cores and coatings, β-crystalline mannitol, microcrystalline cellulose, acidic excipients, disintegrants, lubricants, and binders are employed. Through high-speed wet granulation and tableting processes, particle size and excipient ratios are controlled to reduce impurity content and improve dissolution and stability.
The prepared tablets have low impurity content, high stability, fast disintegration rate, high dissolution rate, small tablet weight difference, good uniformity, high bioavailability, simple process, and reduced cost.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of pharmaceutical formulation technology, specifically to a vonoprazan fumarate tablet, its preparation method, and its uses. Background Technology
[0002] Vonoprazan fumarate is a potassium-competitive acid blocker (P-CAB). Vonoprazan reversibly inhibits H+, K+-ATPase activity through potassium-competitive mechanisms, and can remain in the gastric parietal cells for a prolonged period, thus inhibiting gastric acid production and effectively suppressing the formation of upper gastrointestinal mucosal damage. Its chemical name is 1-[5-(2-fluorophenyl)-1-(pyridin-3-sulfonyl)-1H-pyrrole-3-yl]-N-methylmethylamine monofumarate, and its molecular structure is as follows:
[0003]
[0004] Vonoprazan fumarate (TAK-438, Takecab) is a potassium-competitive acid blocker (P-CAB).
[0005] Vonoprazan fumarate is a novel potassium-competitive acid blocker (P-CAB) developed by Takeda Pharmaceutical Company Limited. It is used to treat acid-related disorders (ARDS) such as Helicobacter pylori infection, gastroesophageal reflux, peptic ulcers, duodenal ulcers, esophagitis, and gastric ulcers. In vitro activity studies show that this compound inhibits the proton pump 400 times more effectively than lansoprazole, and its selectivity relative to Na,K-ATPase is more than 500 times greater. In cultured rabbit gastric gland tissue, TAK-438 showed a higher accumulation rate and slower clearance rate than lansoprazole, resulting in stronger efficacy and longer-lasting acid-suppressing effect in vivo.
[0006] Currently, vonoprazan fumarate is available in tablet form, with strengths of 10 mg and 20 mg (calculated as vonoprazan), and the recommended dose is 20 mg (calculated as vonoprazan).
[0007] Patent CN115364065A discloses a method for preparing vonoprazan fumarate tablets that removes conventional organic acid components and uses acidic alkaline earth metal salts to provide a slightly acidic environment for the API. The alkaline earth metal salts also act as fillers, and the proportions of excipients are specifically adjusted. However, the resulting tablets have poor uniformity, and their dissolution behavior does not meet the limits, making it impossible to prepare qualified tablets.
[0008] Patent CN111973565A discloses a tablet containing vonoprazan fumarate and a method for determining its dissolution rate. The tablets prepared by this method avoid the wet-heat process, and the granules have good flowability and compressibility, are non-sticky, have a smooth surface, meet the acceptable friability requirements, and have stable tablet weight. However, the amount of fumarate used is relatively large, resulting in a large difference in the pH of the resulting tablet microenvironment compared to the reference formulation, and bioinequivalence, making it impossible to obtain qualified tablets.
[0009] Patent CN117462507A addresses the problem of significant stability degradation in existing vonoprazan fumarate pharmaceutical compositions during light exposure, high temperature, and accelerated testing. It provides a vonoprazan fumarate pharmaceutical composition comprising a coating and a tablet core. The coating materials include triacetin and zein, and the tablet core material includes vonoprazan fumarate. However, its active ingredient requires air jet milling, resulting in significant loss; furthermore, the large amount of fumaric acid used leads to a large difference in the pH of the resulting tablet microenvironment compared to the reference formulation, and bioequivalence, making it impossible to obtain qualified tablets.
[0010] Patent CN114053239A provides a vonoprazan fumarate pharmaceutical composition exhibiting high stability under high temperature, high humidity, and strong light irradiation. The composition comprises a coating containing copovidone and a tablet core containing vonoprazan fumarate, with the weight ratio of copovidone in the coating being 5-30%. However, its preparation process involves wet granulation to obtain wet granules, followed by fluidized bed granulation and drying, resulting in a complex process, low yield, and high cost.
[0011] Patent CN107224438A relates to a vonoprazan fumarate pharmaceutical composition, providing a pharmaceutical composition containing the active ingredient vonoprazan fumarate and a method for stabilizing it. The pharmaceutical composition is free of plasticizers and exhibits good formulation stability, showing good stability under high temperature and light exposure. However, the tablets exhibit slow dissolution behavior and poor uniformity, failing to guarantee bioequivalence with a reference formulation.
[0012] Currently, relevant patents for vonoprazan fumarate tablets have been found. Based on the existing patents, the main problems with tablet formulations include:
[0013] 1. Key quality attributes of tablets, such as stability, disintegration or dissolution, tablet weight variation, uniformity, and bioequivalence, cannot be simultaneously considered.
[0014] 2. The preparation process is complex, time-consuming, costly, may have organic solvent residues, and has low production efficiency.
[0015] 3. The existing tablets have a large difference in microenvironment pH compared to the reference formulation, and are bioequivalent, making it impossible to obtain qualified tablets. Summary of the Invention
[0016] To address the aforementioned technical problems, this disclosure provides a vonoprazan fumarate tablet, its preparation method, and its uses. This tablet can reduce the impurity content of the formulation and improve its stability; it also improves the dissolution rate of vonoprazan fumarate; and it has advantages such as rapid disintegration, small tablet weight variation, and uniform content. The preparation method of this disclosure is simple and has advantages such as good stability, good medication compliance, and high bioavailability.
[0017] To achieve the above objectives, the first aspect of this disclosure provides a vonoprazan fumarate tablet, the tablet comprising a tablet core and a coating covering the outer surface of the tablet core;
[0018] Based on the total weight of the core, the raw materials of the core include: 5.0 to 20.0% by weight of vonoprazan fumarate, 65.5 to 90.0% by weight of filler, 0.05 to 1.0% by weight of acidic excipients, 2.0 to 8.0% by weight of disintegrant, 0.5 to 2.5% by weight of lubricant and 0.5 to 3.0% by weight of binder;
[0019] The particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 136 μm, any value of D50 between 10 and 48 μm, and any value of D10 between 6 and 27 μm.
[0020] The filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies any value of D90 between 90 and 236 μm, any value of D50 between 25 and 70 μm, and any value of D10 between 5 and 25 μm.
[0021] The acidic excipient is selected from at least one of tartaric acid, fumaric acid, and citric acid;
[0022] The disintegrant is selected from at least one of sodium carboxymethyl starch, croscarmellose sodium, low-substituted hydroxypropyl cellulose and croscarmellose.
[0023] The lubricant is selected from at least one of magnesium stearate, colloidal silica, calcium stearate, and talc.
[0024] The adhesive is selected from at least one of hydroxypropyl cellulose, hydroxypropyl methylcellulose, povidone, and sodium carboxymethyl cellulose.
[0025] Optionally, the particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 27 μm, any value of D50 between 10 and 14 μm, and any value of D10 between 6 and 8 μm; preferably, the particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm; the filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm; the acidic excipient is fumaric acid; the disintegrant is croscarmellose sodium; the lubricant is magnesium stearate; and the binder is hydroxypropyl cellulose.
[0026] Optionally, based on the total weight of the tablet core, the raw materials of the tablet core include: 5.0–20.0 wt% vonoprazan fumarate, 60.5–75.0 wt% β-mannitol, 5.0–15.0 wt% microcrystalline cellulose, 0.05–1.0 wt% fumaric acid, 2.0–8.0 wt% croscarmellose sodium, 0.5–2.5 wt% magnesium stearate, and 0.5–3.0 wt% hydroxypropyl cellulose; based on the total weight of the tablet, the coating content is 3.0–6.0 wt%; wherein the coating is a gastrointestinal film coating premix.
[0027] Optionally, based on the total weight of the tablet core, the raw materials of the tablet core include: 12.15 wt% vonoprazan fumarate, 70.16 wt% β-mannitol, 10.0 wt% microcrystalline cellulose, 0.1 wt% fumaric acid, 5.0 wt% croscarmellose sodium, 1.5 wt% magnesium stearate, and 1.09 wt% hydroxypropyl cellulose; based on the total weight of the tablet, the coating content is 6.0 wt%.
[0028] Optionally, when the β-crystalline mannitol is characterized by XRD, it exhibits characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
[0029] A second aspect of this disclosure provides a method for preparing the tablet described in the first aspect, the method comprising the following steps:
[0030] S1. The filler, the first disintegrant, and vonoprazan fumarate are mixed and treated to obtain a premixed material;
[0031] S2. Add the premixed material to a high-speed wet granulator, and spray the mixture of acidic auxiliary material solution and binder solution into the high-speed wet granulator for granulation, and collect 20-30 mesh particles by sieving.
[0032] S3. After the particles are mixed with the second disintegrant and lubricant in a second mixing process, the resulting mixture is then subjected to tableting and coating processes in sequence.
[0033] The particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 136 μm, any value of D50 between 10 and 48 μm, and any value of D10 between 6 and 27 μm.
[0034] The filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies any value of D90 between 90 and 236 μm, any value of D50 between 25 and 70 μm, and any value of D10 between 5 and 25 μm.
[0035] Optionally, the particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 27 μm, any value of D50 between 10 and 14 μm, and any value of D10 between 6 and 8 μm; preferably, the particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm.
[0036] The filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm;
[0037] When the β-crystalline mannitol was characterized by XRD, it exhibited characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
[0038] Optionally, in step S1, the content of the first disintegrant is 1 to 2% by weight, based on the total weight of the chip core; the conditions for the first mixing treatment include: a rotation speed of 100 to 150 rpm and a time of 5 to 10 min.
[0039] Optionally, in step S2, the granulation conditions include: an inlet air temperature of 55–65°C, an injection velocity of the mixture of 200–300 rpm, and an air volume of 15–20 m³ / h. 3 / h, moisture content controlled within 1%.
[0040] Optionally, in step S3, the content of the second disintegrant is 1 to 6% by weight, based on the total weight of the chip core; the conditions for the second mixing treatment include: a rotation speed of 10 to 15 rpm and a time of 15 to 30 min.
[0041] A third aspect of this disclosure provides a method for reducing the impurity content in the tablets described in the first aspect, the method comprising the following steps:
[0042] S1. Mix β-crystalline mannitol, microcrystalline cellulose, first disintegrant and vonoprazan fumarate to obtain a premixed material;
[0043] S2. Add the premixed material to a high-speed wet granulator, and spray the mixture of acidic auxiliary material solution and binder solution into the high-speed wet granulator for granulation, and collect 20-30 mesh particles by sieving.
[0044] S3. After the particles are mixed with the second disintegrant and lubricant in a second mixing process, the resulting mixture is then subjected to tableting and coating processes in sequence.
[0045] The particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 27 μm, any value of D50 between 10 and 14 μm, and any value of D10 between 6 and 8 μm.
[0046] The filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies any value of D90 between 90 and 236 μm, any value of D50 between 25 and 70 μm, and any value of D10 between 5 and 25 μm;
[0047] The impurities include impurity D and / or impurity H; impurity D is N-{[5-(2-fluorophenyl)-1-(pyridin-3-yl-sulfonyl)-1H-pyrrolo-3-yl]-methyl}-N-methylaspartic acid, and impurity H is 1-(5-(2-fluorophenyl)-1H-pyrrolo-3-yl)-N-methylmethylamine.
[0048] Optionally, the particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm; the filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm; when the β-crystalline mannitol is characterized by XRD, it has characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
[0049] This disclosure provides, in its fourth aspect, the use of the tablets described in the first aspect or prepared by the method described in the second aspect in the preparation of a medicament for treating reflux esophagitis.
[0050] Optionally, the tablets dissolve at a rate of ≥85% within 30 minutes under the specified dissolution conditions; wherein the dissolution conditions include: using 900 mL of acetate buffer solution at pH 4.5 as the dissolution medium and rotating at 50 rpm.
[0051] Through the above technical solution, this disclosure provides a vonoprazan fumarate tablet, its preparation method, and its uses. This disclosure employs a specific formulation and, combined with its specific preparation method, the resulting tablet has the following beneficial effects:
[0052] (1) The impurity content is low (specifically, the impurity D content is as low as 0.10%, which is significantly lower than the impurity limit standard ≤0.98%, the impurity H was not detected, other single impurities are as low as 0.01%, which is significantly lower than the impurity limit standard ≤0.20%; the total impurities are as low as 0.24%, which is significantly lower than the impurity limit standard ≤2.9%), and the stability is high.
[0053] (2) It has a fast disintegration rate (complete disintegration within 60s), high dissolution rate (up to 100%, significantly higher than the dissolution limit standard ≥85%), and good dissolution behavior;
[0054] (3) The tablet weight difference is small (as low as -1.82 to 1.39%, significantly lower than the limit standard ±7.5%), and the uniformity is high;
[0055] (4) The preparation process is simple, the production efficiency is high, and the cost is significantly reduced.
[0056] (5) It has high bioavailability and is bioequivalent to the reference formulation.
[0057] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Detailed Implementation
[0058] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of this disclosure.
[0059] The first aspect of this disclosure provides a vonoprazan fumarate tablet, the tablet comprising a tablet core and a coating covering the outer surface of the tablet core;
[0060] Based on the total weight of the core, the raw materials of the core include: 5.0 to 20.0% by weight of vonoprazan fumarate, 65.5 to 90.0% by weight of filler, 0.05 to 1.0% by weight of acidic excipients, 2.0 to 8.0% by weight of disintegrant, 0.5 to 2.5% by weight of lubricant and 0.5 to 3.0% by weight of binder.
[0061] The vonoprazan fumarate tablets disclosed herein utilize a specific combination of excipients to prepare tablets that can reduce the impurity content of the formulation product and improve its stability; at the same time, they can improve the dissolution rate of vonoprazan fumarate; and have the advantages of fast disintegration rate, small tablet weight difference, and uniform content; the preparation method of this disclosure is simple and has the advantages of good stability, good drug compliance and high bioavailability.
[0062] In this disclosure, by limiting the content of vonoprazan fumarate within the range of this disclosure, the dissolution rate of the tablets of this disclosure can be further improved. When the content of vonoprazan fumarate is in the range of 5.0 to 20.0% by weight, the prepared tablets exhibit good dissolution behavior, specifically: a dissolution rate of 95% to 100%, significantly higher than the dissolution limit standard ≥85%, and a short disintegration time (complete disintegration within 60 seconds); when the content of vonoprazan fumarate is 12.15% by weight, the prepared tablets exhibit the best dissolution behavior, specifically: the highest dissolution rate (up to 100%, significantly higher than the dissolution limit standard ≥85%), and the tablets completely disintegrate within 60 seconds.
[0063] In one specific embodiment of this disclosure, by controlling the particle size of vonoprazan fumarate to satisfy any value of D90 between 23 and 136 μm, any value of D50 between 10 and 48 μm, and any value of D10 between 6 and 27 μm; preferably, any value of D90 between 23 and 27 μm, any value of D50 between 10 and 14 μm, and any value of D10 between 6 and 8 μm; more preferably, D90 is 25 μm, D50 is 12 μm, and D10 is 7 μm; this can further improve the dissolution and stability of the tablets. Specifically, when the particle size of vonoprazan fumarate is D90 > 136 μm (e.g., D90 = 257 μm), the resulting tablets have unacceptable dissolution and uniformity. When the particle size of vonoprazan fumarate is within the range of this disclosure (especially when D90 = 25 μm), the prepared tablets have the best stability and dissolution behavior, and are bioequivalent to the reference formulation. Specifically, the following characteristics were observed: (1) Best stability: the content of each impurity was the lowest (the content of impurity D was as low as 0.10%, significantly lower than the impurity limit standard ≤0.98%, the content of other single impurities was as low as 0.01%, significantly lower than the impurity limit standard ≤0.20%; the total impurities were as low as 0.24%, significantly lower than the impurity limit standard ≤2.9%); (2) Best dissolution behavior: the shortest disintegration time (complete disintegration in 60s), the highest dissolution rate (up to 100%, significantly higher than the dissolution limit standard ≥85%); and the best fit of the dissolution curve with the reference preparation; (3) the 90% confidence interval of the area under the blood concentration-time curve (AUC) of the peak drug concentration Cmax was between 80% and 125%, which is bioequivalent to the reference preparation.
[0064] In this disclosure, by changing the particle size of the filler mannitol, and limiting the crystal form of mannitol to β-crystalline mannitol and the content of β-crystalline mannitol to within the range of 60.5 to 75.0% by weight, the tablet weight variation can be reduced and the uniformity improved. In one specific embodiment of this disclosure, the filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies any value of D90 between 90 and 236 μm, any value of D50 between 25 and 70 μm, and any value of D10 between 5 and 25 μm. Preferably, the particle size of the β-crystalline mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm. Specifically, when the β-crystalline mannitol is characterized by XRD, characteristic peaks are observed at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°. In the above embodiments, by selecting β-crystalline mannitol that meets the above particle size conditions, the weight variation between tablets can be reduced, and the uniformity of the tablets can be improved. When the mannitol particle size D90 > 236 μm (e.g., D90 = 311 μm), the resulting tablets do not meet the limit standards for weight variation and uniformity, and a qualified product cannot be obtained.
[0065] In a preferred embodiment of this disclosure, when the mannitol particle size is D90 = 142 μm, the tablet weight variation is minimal and the uniformity is highest; specifically, this is manifested in: (1) small tablet weight variation: the tablet weight variation is -1.82 to 1.39%, which is less than the limit standard ±7.5%; (2) high uniformity: the RSD of the mixed uniformity of the tablet intermediates is 1.2%, which is less than the limit standard 5.0%. Furthermore, when β-crystal mannitol is used, the resulting tablets have small tablet weight variation and high stability; when the mannitol crystal form is δ, the resulting tablets have poor stability, and the increase of impurities exceeds the limit, making it impossible to obtain a qualified product.
[0066] In this disclosure, when the prepared tablets contain vonoprazan fumarate and β-mannitol within the particle size range of this disclosure, not only is the stability of the tablets increased, and the dissolution and uniformity significantly improved, but also the specific impurities D and H are significantly reduced. The particle size of vonoprazan fumarate and the crystal form and particle size of mannitol are interrelated and mutually influential factors, and are necessary conditions for solving the technical problems and achieving the technical effects of this disclosure. The vonoprazan fumarate tablets of this disclosure produce the technical effect of significantly improving dissolution and uniformity while reducing the content of impurities D and H.
[0067] In this disclosure, the addition of acidic excipients can further significantly reduce the impurity content in the prepared tablets, thereby significantly improving stability; and the tablets have a short disintegration time and significantly improved dissolution behavior. In a specific embodiment of this disclosure, when the acidic excipient is selected from at least one of tartaric acid, fumaric acid and citric acid, the resulting tablets have good stability and dissolution behavior, specifically: (1) good stability: the content of each impurity is significantly reduced (<0.10%, significantly lower than the impurity limit standard ≤0.98%); (2) good dissolution behavior: the dissolution rate is as high as 98-100%, significantly higher than the limit standard ≥85%, and the disintegration time is short (complete disintegration in 60s); in a preferred embodiment of this disclosure, when the acidic excipient is fumaric acid... The resulting tablets exhibited the best stability and dissolution behavior, specifically: (1) Best stability: the content of each impurity was the lowest (the content of impurity D was as low as 0.10%, significantly lower than the impurity limit standard ≤0.98%, the content of other single impurities was as low as 0.01%, significantly lower than the impurity limit standard ≤0.20%; the total impurities were as low as 0.24%, significantly lower than the impurity limit standard ≤2.9%); (2) Best dissolution behavior: the disintegration time was the shortest (complete disintegration in 60s), and the dissolution rate was the highest (up to 100%, significantly higher than the dissolution rate limit standard ≥85%).
[0068] Furthermore, by controlling the amount of acidic excipients, the content of various impurities can be significantly reduced, thereby improving the stability of the tablets; and the dissolution rate and dissolution behavior can be improved. In one embodiment of this disclosure, when the mass fraction of acidic excipients is 0.05 to 1.0% by weight, the resulting tablets have good stability and dissolution behavior. When the mass fraction of acidic excipients is <0.05% by weight or >1.0% by weight (e.g., the amount of fumaric acid is 0% by weight and 2.5% by weight), it is not equivalent to the reference preparation, and a qualified product cannot be obtained. Among them, when the mass fraction of acidic excipients is 0.1% by weight (e.g., fumaric acid dosage = 0.22 mg / tablet), the stability and dissolution behavior are the best, and the bioequivalence with the reference formulation is as follows: (1) Best stability: the content of each impurity is the lowest (the content of impurity D is as low as 0.10%, which is significantly lower than the impurity limit standard ≤0.98%, the content of other single impurities is as low as 0.01%, which is significantly lower than the impurity limit standard ≤0.20%; the total impurities are as low as 0.24%, which is significantly lower than the impurity limit standard ≤2.9%); (2) Best dissolution behavior: the disintegration time is the shortest (complete disintegration in 60s), and the dissolution rate is the highest (up to 100%, which is significantly higher than the dissolution rate limit standard ≥85%); (3) the 90% confidence interval of the peak concentration Cmax and the area under the blood concentration-time curve AUC are both between 80% and 125%, which is bioequivalent with the reference formulation.
[0069] In this disclosure, by limiting the amount of disintegrant, the time required for complete tablet disintegration can be reduced, dissolution rate can be improved, and dissolution behavior can be enhanced. When the amount of disintegrant is 2.0 to 8.0% by weight of the tablet core material, the resulting tablet exhibits good dissolution behavior. Furthermore, by limiting the type of disintegrant, the dissolution rate of the tablet can be improved, and dissolution behavior can be enhanced. When the disintegrant is selected from at least one of sodium carboxymethyl starch, croscarmellose sodium, low-substituted hydroxypropyl cellulose, and croscarmellose, the resulting tablet exhibits good dissolution behavior.
[0070] In this disclosure, by controlling the amount of lubricant, disintegration effect and dissolution rate can be improved, thus enhancing dissolution behavior; and tablet weight variation can be reduced, improving uniformity; when the lubricant content is controlled at 0.5–2.5% by weight, the resulting tablets exhibit good dissolution behavior. Furthermore, by controlling the type of lubricant, the time required for complete disintegration can be reduced, dissolution rate can be improved, and dissolution behavior can be enhanced; and tablet weight variation can be reduced, improving uniformity; when the lubricant is selected from at least one of magnesium stearate, colloidal silica, calcium stearate, and talc, the resulting tablets exhibit good dissolution behavior, small tablet weight variation, and high uniformity.
[0071] In one specific embodiment of this disclosure, the adhesive is selected from at least one of hydroxypropyl cellulose, hydroxypropyl methylcellulose, povidone, and sodium carboxymethyl cellulose.
[0072] In a preferred embodiment of this disclosure, the particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm; the filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm; the acidic excipient is fumaric acid; the disintegrant is croscarmellose sodium; the lubricant is magnesium stearate; and the binder is hydroxypropyl cellulose.
[0073] In one specific embodiment of this disclosure, based on the total weight of the tablet core, the raw materials of the tablet core include: 5.0–20.0 wt% vonoprazan fumarate, 60.5–75.0 wt% β-mannitol, 5.0–15.0 wt% microcrystalline cellulose, 0.05–1.0 wt% fumaric acid, 2.0–8.0 wt% croscarmellose sodium, 0.5–2.5 wt% magnesium stearate, and 0.5–3.0 wt% hydroxypropyl cellulose; based on the total weight of the tablet, the coating content is 3.0–6.0 wt%; wherein the coating is a gastric-soluble film coating premix.
[0074] In a preferred embodiment of this disclosure, based on the total weight of the tablet core, the raw materials of the tablet core include: 12.15 wt% vonoprazan fumarate, 70.16 wt% β-mannitol, 10.0 wt% microcrystalline cellulose, 0.1 wt% fumaric acid, 5.0 wt% croscarmellose sodium, 1.5 wt% magnesium stearate, and 1.09 wt% hydroxypropyl cellulose; based on the total weight of the tablet, the coating content is 6.0 wt%.
[0075] A second aspect of this disclosure provides a method for preparing the tablet described in the first aspect, the method comprising the following steps:
[0076] S1. The filler, the first disintegrant, and vonoprazan fumarate are mixed and treated to obtain a premixed material;
[0077] S2. Add the premixed material to a high-speed wet granulator, and spray the mixture of acidic auxiliary material solution and binder solution into the high-speed wet granulator for granulation, and collect 20-30 mesh particles by sieving.
[0078] S3. After the particles are mixed with the disintegrant and lubricant in a second mixing process, the resulting mixture is then subjected to tableting and coating processes in sequence.
[0079] The particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 136 μm, any value of D50 between 10 and 48 μm, and any value of D10 between 6 and 27 μm.
[0080] The filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies any value of D90 between 90 and 236 μm, any value of D50 between 25 and 70 μm, and any value of D10 between 5 and 25 μm.
[0081] In this disclosure, a specific formulation and preparation method are used to prepare tablets that have the following beneficial effects:
[0082] (1) The content of impurity D is as low as 0.10%, which is significantly lower than the impurity limit standard ≤0.98%; the content of other single impurities is as low as 0.01%, which is significantly lower than the impurity limit standard ≤0.20%; the total impurities are as low as 0.24%, which is significantly lower than the impurity limit standard ≤2.9%; and the stability is high.
[0083] (2) It has a fast disintegration rate (complete disintegration within 60s), high dissolution rate (up to 100%, significantly higher than the dissolution limit standard ≥85%), and good dissolution behavior;
[0084] (3) Small tablet weight variation (as low as -1.82% to 1.39%) and high uniformity;
[0085] (4) The preparation process is simple, the production efficiency is high, and the cost is significantly reduced;
[0086] (5) It has high bioavailability and is more equivalent to the reference formulation.
[0087] In one specific embodiment of this disclosure, the particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 27 μm, any value of D50 between 10 and 14 μm, and any value of D10 between 6 and 8 μm; preferably, the particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm; the filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies... The D90 is 142 μm, the D50 is 63 μm, and the D10 is 25 μm. When the β-crystalline mannitol is characterized by XRD, it has characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
[0088] In one specific embodiment of this disclosure, in step S1, the content of the first disintegrant is 1 to 2% by weight, based on the total weight of the chip core.
[0089] In one specific embodiment of this disclosure, the conditions for the first mixing process include: a rotation speed of 100-150 rpm and a time of 5-10 min.
[0090] In one specific embodiment of this disclosure, in step S2, the granulation conditions include: an inlet air temperature of 55–65°C, an injection velocity of the mixed liquid of 200–300 rpm, and an air volume of 15–20 m³ / h. 3 / h; In the above embodiments, the moisture content can be controlled to within 1%.
[0091] According to this disclosure, in step S2, the method for preparing the acidic excipient solution includes adding 0.05 to 1.0 g of acidic excipient to every 100 mL (80 to 100°C) of water. The method for preparing the adhesive solution includes adding 5.0 to 10.0 g of adhesive to every 100 mL of water.
[0092] In one specific embodiment of this disclosure, in step S3, the content of the second disintegrant is 1 to 6% by weight, based on the total weight of the chip core.
[0093] In one specific embodiment of this disclosure, the conditions for the second mixing process include: a rotation speed of 10–15 rpm and a time of 15–30 min. In the above embodiment, the uniformity of the mixture can be ensured, thereby ensuring the uniformity of the content of the finished product.
[0094] In this disclosure, the tableting process includes: compressing the mixture using a tablet mold (11×6mm) to form tablets with a hardness of 80N-120N, a single tablet weighing approximately 0.22g, and a single tablet achieving the recommended dose of 20mg (calculated as vonoprazan).
[0095] In this disclosure, the coating process includes: turning on the pneumatic stirrer, placing purified water in a stainless steel tank, slowly adding a gastric-soluble film coating premix to disperse it evenly, and stirring until dissolved. The tableted material is then placed into a coating pan, preheated (45–75°C), coated, with a coating weight gain of approximately 3.0%–6.0%, and the spraying process is stopped.
[0096] A third aspect of this disclosure provides a method for reducing the impurity content in the tablets described in the first aspect, the method comprising the following steps:
[0097] S1. Mix β-crystalline mannitol, microcrystalline cellulose, first disintegrant and vonoprazan fumarate to obtain a premixed material;
[0098] S2. Add the premixed material to a high-speed wet granulator, and spray the mixture of acidic auxiliary material solution and binder solution into the high-speed wet granulator for granulation, and collect 20-30 mesh particles by sieving.
[0099] S3. After the particles are mixed with the second disintegrant and lubricant in a second mixing process, the resulting mixture is then subjected to tableting and coating processes in sequence.
[0100] The particle size of the vonoprazan fumarate satisfies any value of D90 between 23 and 27 μm, any value of D50 between 10 and 14 μm, and any value of D10 between 6 and 8 μm.
[0101] The filler is β-crystalline mannitol and microcrystalline cellulose, wherein the particle size of the β-crystalline mannitol satisfies any value of D90 between 90 and 236 μm, any value of D50 between 25 and 70 μm, and any value of D10 between 5 and 25 μm;
[0102] The impurities include impurity D and / or impurity H; impurity D is N-{[5-(2-fluorophenyl)-1-(pyridin-3-yl-sulfonyl)-1H-pyrrolo-3-yl]-methyl}-N-methylaspartic acid, and impurity H is 1-(5-(2-fluorophenyl)-1H-pyrrolo-3-yl)-N-methylmethylamine.
[0103] In a preferred embodiment of this disclosure, the particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm; the filler is β-mannitol and microcrystalline cellulose, wherein the particle size of the β-mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm; when the β-mannitol is characterized by XRD, it has characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
[0104] This disclosure provides, in its fourth aspect, the use of the tablets described in the first aspect or prepared by the method described in the second aspect in the preparation of a medicament for treating reflux esophagitis.
[0105] According to this disclosure, the tablets have a dissolution rate of ≥85% under the following dissolution conditions over 30 minutes: wherein the dissolution conditions include: 900 mL of acetate buffer solution at pH 4.5 as the dissolution medium and a rotation speed of 50 rpm.
[0106] The present disclosure is further described below with reference to embodiments, but the present disclosure is not limited to the following embodiments. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0107] Example 1
[0108] This embodiment illustrates the preparation of vonoprazan fumarate tablets using the method disclosed herein. The types and contents of raw materials and coatings for the tablet core, by mass percentage, are shown in Table 1.
[0109] Table 1
[0110]
[0111] The method for preparing vonoprazan fumarate tablets includes the following steps:
[0112] (1) Premixed:
[0113] β-crystalline mannitol, microcrystalline cellulose, and a portion (1% by weight) of cross-linked sodium carboxymethyl cellulose were mixed with vonoprazan fumarate at a mixing speed of 10 rpm for 10 min to obtain a premixed material.
[0114] (2) Wet granulation:
[0115] First solution: Dissolve fumaric acid in 9 mL of water at 100°C to prepare the first solution;
[0116] Second solution: Dissolve hydroxypropyl cellulose in 29 mL of water, then add the first solution to the second solution and mix well to prepare the second solution.
[0117] The premixed material is added to a high-speed wet granulator, and the second solution is sprayed into the high-speed wet granulator for granulation. The inlet air temperature is set to 60℃, the spraying speed to 18rpm, and the air volume to 35m³ / h. 3 / h, measure moisture at 105℃ for 5min, and control the moisture content to within 1%; collect 20-mesh particles by sieving.
[0118] (3) The granules, the remaining disintegrant and lubricant are mixed for 15 minutes at a mixing speed of 10 rpm, and then the resulting mixture is subjected to tableting and coating processes in sequence.
[0119] The tableting process involves compressing the total granules into tablets using a tablet mold (11×6mm) with a hardness of 80N-120N. Each tablet weighs approximately 0.22g, and a single tablet can achieve the recommended dose of 20mg (calculated as vonoprazan).
[0120] Coating process: Turn on the pneumatic stirrer, place purified water in a stainless steel container, slowly add the gastrointestinal film coating premix and disperse it evenly, stirring until dissolved. Add the tableted material to the coating pan, preheat (60℃), and coat. The coating weight gain is approximately 4.5%. Stop spraying. Tablets S-1 are obtained.
[0121] Example 2
[0122] This example illustrates the effect of vonoprazan fumarate particle size on tablets.
[0123] The raw materials and coating types and contents of the tablet core, as well as the preparation method, are the same as in Example 1, except that:
[0124] (1) Method 1: The particle size of vonoprazan fumarate is 41 μm for D90, 23 μm for D50 and 8 μm for D10; tablet S-2 is obtained.
[0125] (2) Method 2: The particle size of vonoprazan fumarate is D90 136 μm, D50 49 μm and D10 27 μm; tablet S-3 is obtained.
[0126] (3) Method 3: The particle size of vonoprazan fumarate is D90 257 μm, D50 82 μm and D10 34 μm; tablet S-4 is obtained.
[0127] The particle size of vonoprazan fumarate can be altered by using different batches of raw materials or by sieving.
[0128] Example 3
[0129] This example illustrates the effect of particle size of β-crystalline mannitol on tablets.
[0130] The raw materials and coating types and contents of the tablet core, as well as the preparation method, are the same as in Example 1, except that:
[0131] (1) Method 1: The particle size of β-crystalline mannitol is D90 of 44 μm, D50 of 13 μm and D10 of 6 μm; tablet S-5 is obtained.
[0132] (2) Method 2: The particle size of β-crystalline mannitol is D90 of 236 μm, D50 of 79 μm and D10 of 34 μm; tablet S-6 is obtained.
[0133] (3) Method 3: The particle size of β-crystalline mannitol is D90 of 311 μm, D50 of 125 μm and D10 of 69 μm; tablet S-7 is obtained.
[0134] The particle size of β-crystalline mannitol can be altered by selecting different batches of raw materials or by sieving.
[0135] Example 4
[0136] This example illustrates the effect of mannitol crystal size on tablets.
[0137] The raw materials and coating types and contents of the tablet core, as well as the preparation method, are the same as in Example 1, except that:
[0138] (1) Method 1: β-crystalline mannitol (purchased from ROQUETTE, France); tablet S-8 was obtained.
[0139] (2) Method 2: δ crystal form mannitol (purchased from Merck, Germany); tablet S-9 was obtained.
[0140] Example 5
[0141] This example illustrates the effect of adding acidic excipients on tablets.
[0142] The raw materials and coating types and contents of the tablet core, as well as the preparation method, are the same as in Example 1, except that:
[0143] Without adding fumaric acid, hydroxypropyl cellulose was dissolved in 29 mL of water to prepare a solution with a solid content of 6%; tablets S-10 were obtained.
[0144] Example 6
[0145] This example illustrates the effect of the type of acidic excipient added on tablets.
[0146] The raw materials and coating types and contents of the tablet core, as well as the preparation method, are the same as in Example 1, except that:
[0147] (1) Method 1: The acidic excipient is tartaric acid; tablet S-11 is obtained.
[0148] (2) Method 2: The acidic excipient is citric acid; tablet S-12 is obtained.
[0149] (3) Method 3: The acidic excipient is lactic acid; tablet S-13 is obtained.
[0150] (4) Method 4: The acidic excipient is acetic acid; tablet S-14 is obtained.
[0151] Example 7
[0152] This example illustrates the effect of the amount of acidic excipients added on tablets.
[0153] The raw materials and coating types and contents of the tablet core, as well as the preparation method, are the same as in Example 1, except that:
[0154] (1) Method 1: The acidic excipient is 0.05% by weight of fumaric acid; tablet S-15 is obtained.
[0155] (2) Method 2: The acidic excipient is 0.15% by weight of fumaric acid; tablet S-16 is obtained.
[0156] (3) Method 3: The acidic excipient is 0.2% by weight of fumaric acid; tablet S-17 is obtained.
[0157] (4) Method 4: The acidic excipient is 0.5% by weight of fumaric acid; tablet S-18 is obtained.
[0158] Comparative Example 1
[0159] The preparation was carried out using the raw materials of patent CN115364065A, and the specific raw materials are shown in Table 2.
[0160] Comparative Example 1: Vonoprazan fumarate (particle size distribution D90 = 41 μm, D50 = 23 μm, D10 = 8 μm); mannitol (β crystal form, particle size distribution D90 = 44 μm, D50 = 13 μm, D10 = 6 μm).
[0161] Table 2
[0162]
[0163]
[0164] The preparation method is the same as in Example 1, and tablet D-1 is obtained.
[0165] Comparative Example 2
[0166] The raw materials used in the preparation were those specified in patent CN111973565A, as shown in Table 3. In Comparative Example 2, the particle size distribution of vonoprazan fumarate was D90 = 20.12 μm, D50 = 12 μm, and D10 = 7 μm.
[0167] Mannitol (β crystal form, particle size distribution D90 = 236 μm, D50 = 79 μm, D10 = 34 μm).
[0168] Table 3
[0169]
[0170] The preparation method was the same as in Example 1, and tablet D-2 was obtained.
[0171] Comparative Example 3
[0172] The raw materials used in the preparation were those specified in patent CN118078767A, as shown in Table 4.
[0173] Table 4
[0174]
[0175]
[0176] Among them, vonoprazan fumarate (particle size distribution D90 = 41 μm, D50 = 23 μm, D10 = 8 μm); in method 1, β-crystalline mannitol with particle size distribution D90 = 311 μm, D50 = 125 μm, D10 = 69 μm was used, and the preparation method was the same as in Example 1 to obtain tablet D-3;
[0177] In Method 2, a mixture of α-crystalline mannitol and β-crystalline mannitol was used, with a mass ratio of α-crystalline mannitol to β-crystalline mannitol of 0.41. The particle size distribution of β-crystalline mannitol was D90 = 311 μm, D50 = 125 μm, and D10 = 69 μm, while that of α-crystalline mannitol was D90 = 268 μm, D50 = 110 μm, and D10 = 52 μm. The preparation method was the same as in Example 1, resulting in tablet D-4.
[0178] Test Example 1
[0179] This example is used to illustrate the stability of the tablets in the examples and comparative examples.
[0180] The contents and stability of the preparations prepared in the following examples were determined by high performance liquid chromatography (General Chapter 0512 of the Chinese Pharmacopoeia 2020 edition) under fresh preparation conditions (0 days) and under different conditions for 30 days. The results are shown in Table 5.
[0181] Impurity D: Process and degradation impurity, chemical name: N-{[5-(2-fluorophenyl)-1-(pyridin-3-yl-sulfonyl)-1H-pyrrolo-3-yl]-methyl}-N-methylaspartic acid, structural formula:
[0182]
[0183] Impurity H: Process and degradation impurity, chemical name: 1-(5-(2-fluorophenyl)-1H-pyrrolo-3-yl)-N-methylmethylamine, structural formula:
[0184]
[0185] Placement conditions:
[0186] 1) Place at a high temperature of 40℃ for 30 days;
[0187] 2) Place under high humidity conditions (75%) for 30 days;
[0188] 3) Place the product under a light intensity of 4500±500 Lx for 30 days.
[0189] Table 5
[0190]
[0191]
[0192] Test Example 2
[0193] This example is used to illustrate the dissolution rate of the tablets in the examples and comparative examples.
[0194] The dissolution and release were determined according to the method of General Chapter 0931, Method II of the Chinese Pharmacopoeia 2020 Edition. The state of the sample in the dissolution vessel was observed during the dissolution process. The dissolution medium was pH 4.5 acetate buffer. The results are shown in Table 6.
[0195] Table 6
[0196]
[0197] Test Example 3
[0198] This example illustrates the pH of the microenvironment during the dissolution of the intermediate.
[0199] Adding acidic excipients to tablet formulations can significantly improve dissolution and stability. Therefore, to verify the mechanism by which adding acidic excipients improves stability and dissolution behavior, the pH value of the tablet intermediate microenvironment in the examples was measured. The results showed that the pH of the tablet intermediate microenvironment in different formulations was significantly different.
[0200] The study found that the main factors affecting the pH of the microenvironment during tablet dissolution were the addition of acidic excipients and their types and amounts; while other excipient components had little effect on the pH of the microenvironment (i.e., intermediate pH) during tablet dissolution. Therefore, the pH values of the intermediate microenvironment in Examples 1, 5, 6, 7 and Comparative Example 2 were further tested.
[0201] The experimental procedure was as follows: the tablets in the examples were completely transferred to test tubes containing 10 mL of purified water, dissolved by sonication, and the pH in the intermediate microenvironment was measured. The results are shown in Table 7.
[0202] Table 7
[0203]
[0204] Test Example 4
[0205] This example illustrates the weight differences of uncoated tablets.
[0206] Twenty tablets of each of the tablets prepared in the above examples were taken for tablet weight variation testing (i.e., the weight difference between each tablet). Better particle uniformity, better particle flowability, and more uniform compression resulted in smaller tablet weight variations; that is, the more uniform the weight of the tablets, the more accurate the content of the active pharmaceutical ingredient in the tablet. Conversely, a larger tablet weight variation indicated a greater difference in the content of the active pharmaceutical ingredient in the tablet. The limit for tablet weight variation was ±7.5%. The results are shown in Table 8.
[0207] Table 8
[0208]
[0209]
[0210] Test Example 5
[0211] This example illustrates the dissolution profile of a tablet.
[0212] The particle size of the active ingredient and the amount of fumaric acid in the tablet formulation have a significant impact on the dissolution behavior of the sample. Therefore, in order to verify the above variables and the related mechanism of dissolution behavior, the dissolution curves of the tablets in the corresponding examples were detected. The results showed that the dissolution curves of the formulation samples of different examples had significant differences.
[0213] The study found that the main factor affecting the dissolution behavior of tablets is the particle size of the active ingredient; while other excipients have little effect on the disintegration and dissolution behavior of tablets. Therefore, the dissolution curves of Examples 4, 5, Comparative Example 1 and Comparative Example 2 were further tested.
[0214] The experimental procedure was as follows: Referring to Method II of Section 0931, Determination of Dissolution and Release, General Chapter IV of the 2020 edition of the Chinese Pharmacopoeia, the paddle method was used. The reference formulation and the tablets from the examples were placed in the dissolution apparatus. The medium volume was 900 ml, the rotation speed was 50 rpm, and the dissolution medium was pH 4.5 acetate buffer. The results are shown in Table 9.
[0215] Table 9
[0216]
[0217]
[0218] Test Example 6
[0219] This example illustrates the uniformity of tablet mixing.
[0220] The active ingredients and fillers in the tablet formulation can significantly affect the mixing uniformity. Therefore, in order to verify the correlation mechanism between the active ingredients and fillers and the mixing uniformity, the mixing uniformity of the tablet intermediates in the examples was tested. The results showed that there were significant differences in the mixing uniformity of the intermediates.
[0221] The study found that the main factors affecting the uniformity of tablet mixing are the particle size of the active ingredient and the particle size of the filler; while other excipients have little effect on the uniformity of tablet mixing. Therefore, the uniformity of intermediate mixing in Examples 5, 6 and Comparative Example 1 was further tested.
[0222] The experimental procedure was as follows: samples were taken from different locations in the tablet intermediate mixture in the examples, with 10 sampling locations and a sample size of 1 to 3 times the detection amount. The content was determined by high performance liquid chromatography, and the RSD values of the 10 contents were used to evaluate the mixing uniformity of the intermediate. The results are shown in Table 10.
[0223] Table 10
[0224]
[0225] Test Example 7
[0226] This example illustrates the effect of mannitol crystal form on tablets.
[0227] In tablet formulations, fillers can significantly improve dissolution and stability. Therefore, to verify the mechanism by which fillers improve stability and dissolution behavior, the crystal form of the fillers in the examples was tested. The results showed that the crystal form of the filler had a significant impact on the formulation results.
[0228] The study found that the main factors affecting the crystal form of fillers are: mannitol prepared by different manufacturers has different crystal forms (Example 7); while other excipients have little effect on the crystal form of tablets. Therefore, the crystal form of Example 7 was further tested.
[0229] The experimental procedure was as follows: the crystal form of the tablets in the examples was detected by X-ray powder diffraction, and the results are shown in Figure 11.
[0230] Table 11
[0231]
[0232]
[0233] Test Example 8
[0234] This example illustrates the bioequivalence of tablets.
[0235] The amount of acidic excipients, the type and particle size of fillers, and the amount and particle size of active ingredients in tablet formulations can significantly improve the bioequivalence of self-made samples and reference formulations. Therefore, in order to verify the relevant mechanism of formulation bioequivalence, the bioequivalence of the tablets in the examples and comparative examples with the reference formulations was tested.
[0236] The study was a single-center, randomized, open-label, single-dose, two-formulation, two-sequence, two-period crossover bioequivalence study of vonoprazan fumarate tablets in healthy adult subjects in China. The study examined the single oral (fasting / postprandial) administration of the test formulation vonoprazan fumarate tablets (specification: 20 mg, manufactured by Yuekang Pharmaceutical Group Co., Ltd.) and the reference formulation vonoprazan fumarate tablets (trade name: [not specified]). Specification: 20mg (Certified by Takeda Pharmaceutical Company Limited). This study investigated the relative bioavailability of the two formulations in healthy Chinese subjects, analyzed their pharmacokinetic parameters, and evaluated their bioequivalence. The study was conducted in two parts: Part 1 was a bioequivalence study of the test formulation and the reference formulation administered once on an empty stomach in healthy Chinese adults; Part 2 was a bioequivalence study of the test formulation and the reference formulation administered once after a meal in healthy Chinese adults. The results are shown in Tables 12 and 13.
[0237] Table 12 Statistical results of pharmacokinetic data of vonoprazine in fasting tests
[0238]
[0239] Table 13 Statistical results of pharmacokinetic data of vonoprazine in postprandial trials
[0240]
[0241] Remark:
[0242] T max The time it takes for the drug to reach peak plasma concentration after administration;
[0243] C max Peak blood concentration of the drug after administration;
[0244] AUC last Area under the blood drug concentration-time curve from zero to infinity;
[0245] AUC INF_obs Area under the blood drug concentration-time curve from zero to the final measurable concentration;
[0246] CI_90_Lower~Upper: Lower and upper limits of the 90% confidence interval;
[0247] in conclusion:
[0248] In Example 1, the 90% confidence intervals of the peak concentration (Cmax) on an empty stomach and after a meal, as well as the area under the plasma concentration-time curve (AUC), were both between 80% and 125%, which is equivalent to the reference formulation.
[0249] Results Analysis: The stability, dissolution results, microenvironment pH during intermediate dissolution, tablet weight differences, dissolution curves, mixing uniformity, crystal form, and bioequivalence of the tablets in the above embodiments were analyzed. The effects of the type, dosage, type, particle size of acidic excipients, fillers, active ingredients, disintegrants, and lubricants in the tablet components, as well as the preparation process, on the tablets were investigated.
[0250] I. In order to investigate the effect of the particle size of the active ingredient on the quality of the tablet, based on the active ingredient (calculated as vonoprazan fumarate) of 12.1% by weight in the tablet of Example 1, tablets were prepared by changing the particle size of the active ingredient for comparison.
[0251] 1. The differences are shown in Table 14:
[0252] Table 14
[0253]
[0254]
[0255] 2. Formulation comparisons are shown in Table 15-19:
[0256] Table 15
[0257]
[0258] Table 16
[0259]
[0260] Table 17
[0261]
[0262] Table 18
[0263]
[0264] Table 19
[0265]
[0266] The following conclusions can be drawn from the above data:
[0267] (1) The results of impurity content show:
[0268] Under fresh preparation conditions (0 days):
[0269] The impurity D contents of Example 1 (particle size D90 = 25 μm), Example 2 Method 1 (particle size D90 = 41 μm), Example 2 Method 2 (particle size D90 = 136 μm), and Example 2 Method 3 (particle size D90 = 257 μm) were 0.10%, 0.08%, 0.09%, and 0.09%, respectively, which are far below the limit standard (≤0.98%). The impurity H contents were all undetectable, far below the limit standard (≤0.20%). The maximum single impurity content was 0.01%, far below the limit standard (≤0.20%). The total impurity contents were 0.24%, 0.21%, 0.22%, and 0.22%, respectively, far below the limit standard (≤2.9%), indicating good stability.
[0270] Placed at 40℃ for 30 days:
[0271] The impurity D content in Example 1 (particle size D90 = 25 μm), Method 1 of Example 2 (particle size D90 = 41 μm), Method 2 of Example 2 (particle size D90 = 136 μm), and Method 3 of Example 2 (particle size D90 = 257 μm) was 0.09%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.23%, 0.22%, 0.23%, and 0.23%, respectively, far below the limit standard (≤2.9%), indicating good stability.
[0272] Placed for 30 days under high humidity (75%):
[0273] The impurity D contents of Example 1 (particle size D90 = 25 μm), Example 2 Method 1 (particle size D90 = 41 μm), Example 2 Method 2 (particle size D90 = 136 μm), and Example 2 Method 3 (particle size D90 = 257 μm) were 0.10%, 0.07%, 0.08%, and 0.08%, respectively, which are far below the limit standard (≤0.98%). The impurity H contents were all undetectable, far below the limit standard (≤0.20%). The maximum single impurity content was 0.01%, far below the limit standard (≤0.20%). The total impurity contents were 0.24%, 0.24%, 0.21%, and 0.21%, respectively, far below the limit standard (≤2.9%), indicating good stability.
[0274] Placed under 4500±500 Lx light for 30 days:
[0275] The impurity D content in Example 1 (particle size D90 = 25 μm), Method 1 of Example 2 (particle size D90 = 41 μm), Method 2 of Example 2 (particle size D90 = 136 μm), and Method 3 of Example 2 (particle size D90 = 257 μm) was 0.08%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.22%, 0.22%, 0.22%, and 0.20%, respectively, far below the limit standard (≤2.9%), indicating good stability.
[0276] The above results indicate that, using the product formulation disclosed herein, tablet products with good stability can be obtained regardless of the particle size of the active pharmaceutical ingredient.
[0277] (2) The dissolution behavior results show that:
[0278] The formulation obtained in Example 1 (particle size D90 = 25 μm) completely disintegrated in 60 s with a small amount of buildup at the bottom of the container, and the dissolution rate was 100%, which is far above the dissolution limit (≥85%), indicating good and significant dissolution behavior.
[0279] The formulations obtained by Method 1 of Example 2 (particle size D90 = 41 μm) and Method 2 of Example 2 (particle size D90 = 136 μm) completely disintegrated in 60 seconds, with a small amount of accumulation at the bottom of the cup, and the dissolution rate was 90-98%. This was slightly lower than the dissolution rate of Example 1 (particle size D90 = 25 μm), but the dissolution rate was still significantly higher than the dissolution limit (≥85%), indicating good dissolution behavior.
[0280] The formulation obtained by Method 3 in Example 2 (particle size D90 = 257 μm) completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the cup. The dissolution rate was 76%, which was lower than the dissolution limit (≥85%). The dissolution was unqualified, and a qualified tablet product could not be obtained.
[0281] (3) Results of tablet weight difference show:
[0282] The tablets prepared in Example 1 (particle size D90 = 25 μm) have good compressibility, more uniform filling weight, and small tablet weight variation, ranging from -1.82% to 1.39%, which is significantly less than the limit standard ±7.5%.
[0283] The tablets prepared by Method 1 of Example 2 (particle size D90 = 41 μm), Method 2 of Example 2 (particle size D90 = 136 μm), and Method 3 of Example 2 (particle size D90 = 257 μm) had a tablet weight variation controlled within -3.74% to 3.48%, which was slightly higher but still within the limit standard ±7.5%.
[0284] The above results indicate that, using the product formulation disclosed in this invention, tablet products with excellent differences in tablet weight and meeting the limit standards can be obtained with different particle sizes of the active pharmaceutical ingredients.
[0285] (4) The dissolution curve results show:
[0286] The tablets prepared in Example 1 (particle size D90 = 25 μm) showed dissolution rates of 71%, 90%, and 96% at 5 min, 10 min, and 15 min, respectively, under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, and rotation speed: 50 rpm. These results were essentially consistent with the reference formulation (dissolution rates of 73%, 91%, and 97% at 5 min, 10 min, and 15 min, respectively). The dissolution rate at 15 min was greater than 85%, indicating extremely rapid dissolution.
[0287] The tablets prepared by method 1 (particle size D90 = 41 μm) in Example 2 showed basically consistent dissolution at each time point compared with the reference formulation and Example 1 under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, and rotation speed: 50 rpm. Although the dissolution of method 2 (particle size D90 = 136 μm) in Example 2 (65% and 78% at 5 min and 10 min, respectively) was slightly slower than that of the reference formulation (73% and 91% at 5 min and 10 min, respectively), the dissolution rate at 15 min was 90%, which is greater than 85%, and is still considered to be extremely rapid dissolution.
[0288] The tablets prepared by method 3 (particle size D90 = 257 μm) in Example 2, under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, rotation speed: 50 rpm, had a dissolution rate of only 77% at 15 min compared with the reference preparation and Example 1, which did not meet the requirement of a dissolution rate greater than 85% at 15 min. It was significantly slower than Example 1 and inconsistent with the dissolution of the reference preparation.
[0289] The above results indicate that, using the product formulation disclosed herein, different particle sizes of the active pharmaceutical ingredient have a significant impact on the dissolution of the formulation samples. The tablets prepared in Example 1 (particle size D90 = 25 μm), Example 2 (method 1, particle size D90 = 41 μm), and Example 2 (method 2, particle size D90 = 136 μm) exhibit significantly better dissolution behavior than the tablets prepared in Example 2 (method 3, particle size D90 = 257 μm); furthermore, Example 2 (method 3, particle size D90 = 257 μm) could not produce tablets with satisfactory dissolution behavior.
[0290] (5) The results of the mixing uniformity show that:
[0291] The tablet intermediates prepared by Example 1 (particle size D90 = 25 μm), Example 2 by Method 1 (particle size D90 = 41 μm), and Example 2 by Method 2 (particle size D90 = 136 μm) had mixing uniformity RSD values of 1.2%, 1.3%, and 3.5%, respectively, which are far below the limit standard (≤5.0%).
[0292] The tablet intermediate prepared by method 3 (particle size D90 = 257 μm) in Example 2 had a mixing uniformity RSD value of 5.7%, which exceeded the limit standard (≤5.0%), and therefore could not yield a qualified product.
[0293] In summary: ① The active ingredient particle size disclosed herein (e.g., D90: 25–136 μm) can be used to prepare tablets with good stability, dissolution behavior, and uniformity; ② Among these, when the active ingredient particle size used is (e.g., D90 = 25 μm), the prepared tablets (e.g., Example 1) exhibit the best stability, dissolution behavior, uniformity, and bioequivalence; ③ Conversely, when an active ingredient particle size other than that disclosed herein is used (e.g., D90 = 257 μm), the obtained tablets have poor uniformity and dissolution behavior, and qualified tablets cannot be obtained.
[0294] II. In order to investigate the effect of filler particle size on tablet quality, based on the filler content of 70.16% by weight in Example 1, tablets were prepared by changing the particle size of mannitol for comparison.
[0295] 1. The differences are shown in Table 20:
[0296] Table 20
[0297]
[0298] 2. Formulation comparisons are shown in Table 21-24:
[0299] Table 21
[0300]
[0301] Table 22
[0302]
[0303] Table 23
[0304]
[0305] Table 24
[0306]
[0307] The following conclusions can be drawn from the above data:
[0308] (1) The results of impurity content show:
[0309] Under fresh preparation conditions (0 days):
[0310] The impurity D content of Example 1 (particle size D90 = 142 μm), Method 1 of Example 3 (particle size D90 = 44 μm), Method 2 of Example 3 (particle size D90 = 236 μm), and Method 3 of Example 3 (particle size D90 = 311 μm) was 0.07–0.10%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.21–0.24%, far below the limit standard (≤2.9%), and the stability was good.
[0311] Placed at 40℃ for 30 days:
[0312] The impurity D content in Example 1 (particle size D90 = 142 μm), Method 1 of Example 3 (particle size D90 = 44 μm), Method 2 of Example 3 (particle size D90 = 236 μm), and Method 3 of Example 3 (particle size D90 = 311 μm) was 0.09%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.21-0.23%, far below the limit standard (≤2.9%), and the stability was good.
[0313] Placed for 30 days under high humidity (75%):
[0314] The impurity D content of Example 1 (particle size D90 = 142 μm), Method 1 of Example 3 (particle size D90 = 44 μm), Method 2 of Example 3 (particle size D90 = 236 μm), and Method 3 of Example 3 (particle size D90 = 311 μm) was 0.07–0.10%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.20–0.24%, far below the limit standard (≤2.9%), and the stability was good.
[0315] Placed under 4500±500 Lx light for 30 days:
[0316] The impurity D content in Example 1 (particle size D90 = 142 μm), Method 1 of Example 3 (particle size D90 = 44 μm), Method 2 of Example 3 (particle size D90 = 236 μm), and Method 3 of Example 3 (particle size D90 = 311 μm) was 0.08%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.22%, far below the limit standard (≤2.9%), indicating good stability.
[0317] The above results indicate that, using the product formulation disclosed herein, tablet products with good stability can be obtained regardless of the particle size of the filler.
[0318] (2) The dissolution behavior results show that:
[0319] The formulation obtained in Example 1 (particle size D90 = 142 μm) completely disintegrated in 60 s with a small amount of buildup at the bottom of the container, and the dissolution rate was 100%, which is far above the dissolution limit (≥85%), indicating good and significant dissolution behavior.
[0320] The formulations obtained by Method 1 of Example 3 (particle size D90 = 44 μm), Method 2 of Example 3 (particle size D90 = 236 μm), and Method 3 of Example 3 (particle size D90 = 311 μm) completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the container. The dissolution rate was 95-98%, which was significantly higher than the dissolution limit (≥85%), indicating good dissolution behavior.
[0321] The above results indicate that, using the product formulation disclosed herein, tablets with good dissolution behavior can be obtained regardless of the particle size of the filler.
[0322] (3) Results of tablet weight difference show:
[0323] The tablets prepared in Example 1 (particle size D90 = 142 μm) have good compressibility, more uniform filling weight, and small tablet weight variation, ranging from -1.82% to 1.39%, which is significantly less than the limit standard ±7.5%.
[0324] The tablets prepared by Method 1 (particle size D90 = 44 μm) in Example 3 and Method 2 (particle size D90 = 236 μm) in Example 3 had a tablet weight variation controlled within -3.28% to 3.17%, which was slightly higher but still within the limit standard ±7.5%.
[0325] The tablets prepared by method 3 (particle size D90 = 311 μm) in Example 3 had a tablet weight variation controlled between -6.58% and 5.79%, which exceeded the limit standard of ±7.5%, and therefore could not be qualified products.
[0326] The above results show that, using the product formulation disclosed herein, different filler particle sizes have a significant impact on the difference in tablet weight. Qualified products can be obtained from Example 1 (particle size D90 = 142 μm), Example 3 Method 1 (particle size D90 = 44 μm), and Example 3 Method 2 (particle size D90 = 236 μm).
[0327] (4) The results of the mixing uniformity show that:
[0328] The tablet intermediates prepared by Example 1 (particle size D90 = 142 μm), Method 1 of Example 3 (particle size D90 = 44 μm), and Method 2 of Example 3 (particle size D90 = 236 μm) had a mixing uniformity content RSD value of 1.2% to 2.8%, which is far below the limit standard (≤5.0%).
[0329] The tablet intermediate prepared by method 3 (particle size D90 = 311 μm) in Example 3 had a mixing uniformity RSD value of 6.1%, which exceeded the limit standard (≤5.0%), and therefore could not yield a qualified product.
[0330] In summary, ① using the mannitol particle size disclosed herein (e.g., D90: 44–236 μm) can produce tablets with good stability, dissolution behavior, uniformity, and tablet weight variation; ② among which, when a mannitol particle size (e.g., D90 = 142 μm) is used, the prepared tablets (e.g., Example 1) exhibit the best stability, dissolution behavior, uniformity, and tablet weight variation; ③ conversely, when a mannitol particle size other than that disclosed herein (e.g., D90 = 311 μm) is used, the obtained tablets have poor uniformity and tablet weight variation, and qualified tablets cannot be obtained.
[0331] III. In order to investigate the effect of the crystal form of the filler on the quality of the tablet, based on the 70.16% by weight of the filler in the tablet of Example 1, tablets were prepared by changing the crystal form of mannitol for comparison.
[0332] 1. The differences are shown in Table 25:
[0333] Table 25
[0334]
[0335] 2. Formulation comparisons are shown in Table 26-29:
[0336] Table 26
[0337]
[0338]
[0339] Table 27
[0340]
[0341] Table 28
[0342]
[0343] Table 29
[0344]
[0345]
[0346] The following conclusions can be drawn from the above data:
[0347] (1) The results of impurity content show:
[0348] Under fresh preparation conditions (0 days):
[0349] The impurity D content in Example 1 (crystal form = β, Qingdao Mingyue), Method 1 of Example 4 (crystal form = β, ROQUETTE, France), and Method 2 of Example 4 (crystal form = δ, Merck, Germany) was 0.10%, 0.08%, and 0.10%, respectively, which are far below the limit standard (≤0.98%); the impurity H content was undetectable in all cases, which are far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.24%, 0.20%, and 0.24%, respectively, which are far below the limit standard (≤2.9%).
[0350] Placed at 40℃ for 30 days:
[0351] The impurity D content of Example 1 (crystal form = β, Qingdao Mingyue) and Example 4 Method 1 (crystal form = β, ROQUETTE, France) was 0.09% and 0.10%, respectively, which are far below the limit standard (≤0.98%); the impurity H content was undetectable in both cases, which are far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.23% and 0.21%, respectively, which are far below the limit standard (≤2.9%), indicating good stability.
[0352] In Example 4, Method 2 (crystal form = δ, Merck, Germany), the impurity D content was 1.09%, exceeding the limit standard (≤0.98%); the impurity H content was 0.25%, exceeding the limit standard (≤0.20%); the maximum content of other single impurities was 0.34%, exceeding the limit standard (≤0.20%); and the total impurity content was 1.78%, below the limit standard (≤2.9%).
[0353] Placed for 30 days under high humidity (75%):
[0354] The impurity D content of Example 1 (crystal form = β, Qingdao Mingyue) and Example 4, Method 1 (crystal form = β, ROQUETTE, France) was 0.10% and 0.07%, respectively, far below the limit standard (≤0.98%); the impurity H content was undetectable in both cases, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.24% and 0.21%, respectively, far below the limit standard (≤2.9%), indicating good stability.
[0355] In Example 4, Method 2 (crystal form = δ, Merck, Germany), the impurity D content was 1.22%, exceeding the limit standard (≤0.98%); the impurity H content was 0.24%, exceeding the limit standard (≤0.20%); the maximum content of other single impurities was 0.23%, exceeding the limit standard (≤0.20%); and the total impurity content was 1.75%, below the limit standard (≤2.9%).
[0356] Placed under 4500±500 Lx light for 30 days:
[0357] The impurity D content of both Example 1 (crystal form = β, Qingdao Mingyue) and Example 4, Method 1 (crystal form = β, ROQUETTE, France) was 0.08%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.22%, far below the limit standard (≤2.9%), indicating good stability.
[0358] In Example 4, Method 2 (crystal form = δ, Merck, Germany), the impurity D content was 1.15%, exceeding the limit standard (≤0.98%); the impurity H content was 0.21%, exceeding the limit standard (≤0.20%); the maximum content of other single impurities was 0.18%, below the limit standard (≤0.20%); and the total impurity content was 1.63%, below the limit standard (≤2.9%).
[0359] The above results indicate that, using the product formulation disclosed herein, different filler crystal forms affect the stability of the samples. Example 1 (crystal form = β, Qingdao Mingyue) and Example 4, Method 1 (crystal form = β, ROQUETTE, France) both yielded tablet products with good stability. Example 4, Method 2 (crystal form = δ, Merck, Germany) had impurity content exceeding the limit standard, making it impossible to obtain qualified tablets.
[0360] (2) The dissolution behavior results show that:
[0361] The formulation obtained in Example 1 (crystal form = β, Qingdao Mingyue) completely disintegrated in 60s with a small amount of buildup at the bottom of the cup, and the dissolution rate was 100%, which is far higher than the dissolution limit (≥85%), and the dissolution behavior was good and significant.
[0362] The formulations obtained by Method 1 of Example 4 (crystal form = β, ROQUETTE, France) and Method 2 of Example 4 (crystal form = δ, Merck, Germany) completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the vessel, and dissolution rates of 95% and 92%, respectively, which were significantly higher than the dissolution limit (≥85%), indicating good dissolution behavior.
[0363] The above results indicate that, using the product formulation disclosed herein, different filler crystal forms can all produce tablet products with good dissolution behavior.
[0364] (3) Results of tablet weight difference show:
[0365] The tablets prepared in Example 1 (crystal form = β, Qingdao Mingyue) have good compressibility, more uniform filling weight, and small tablet weight difference, which is only -1.82% to 1.39%, significantly less than the limit standard ±7.5%.
[0366] The tablets obtained by Method 1 (crystal form = β, ROQUETTE, France) and Method 2 (crystal form = δ, Merck, Germany) in Example 4 have good compressibility, uniform filling weight, and small tablet weight differences.
[0367] The above results indicate that, using the product formulation disclosed herein, different filler crystal forms can all yield tablet products with good differences in tablet weight.
[0368] (4) Crystal form results show:
[0369] Both Example 1 (crystal form = β, Qingdao Mingyue) and Example 4 Method 1 (crystal form = β, ROQUETTE, France) are of the β type and have obvious characteristic peaks. The 2θ (degrees) are 10.468, 11.430, 14.627, 16.799, 21.685, 25.919, 26.610, 28.177, 31.750, 32.663, 33.602, 38.707, and 44.098, respectively.
[0370] The crystal form of Method 2 in Example 4 (crystal form = δ, Merck, Germany) is inconsistent with that of Example 1 (crystal form = β, Qingdao Mingyue) and Method 3 in Example 4 (crystal form = β, reference formulation). It exhibits distinct characteristic peaks with 2θ (degrees) of 19.396, 22.012, 27.813, and 32.057, respectively.
[0371] In summary, ① using the filler crystal form of this disclosure (crystal form = β, Qingdao Mingyue) can prepare tablets with good stability, dissolution behavior, and tablet weight variation; ② conversely, tablets obtained by using filler crystal forms other than those disclosed in this disclosure (e.g., crystal form = δ, Method 2 of Example 4, Merck, Germany) may meet the standard for impurities for 0 days, but impurities increase significantly during the stability process and exceed the limit, making it impossible to obtain qualified tablets.
[0372] IV. In order to explore the necessity of adding acidic excipients to tablet components, the components of Example 1 were prepared with acidic excipients added, while the acidic excipients and corresponding preparation process of Example 5 were omitted. Then, tablets were prepared by one-step granulation, and the tablets prepared by the two were compared.
[0373] 1. The differences are shown in Table 30:
[0374] Table 30
[0375] Example acidic excipients Example 1 fumaric acid Example 5 none
[0376] 2. Formulation comparisons are shown in Tables 31-36:
[0377] Table 31
[0378]
[0379] Table 32
[0380]
[0381] Table 33
[0382] sample intermediate pH Example 1 4.02 Example 5 5.26
[0383] Table 34
[0384]
[0385] Table 35 Statistical results of pharmacokinetic data of vonoprazine in fasting trials
[0386]
[0387] Table 36 Statistical results of pharmacokinetic data of vonoprazine in postprandial trials
[0388]
[0389] Remark:
[0390] T max The time it takes for the drug to reach peak plasma concentration after administration;
[0391] C max Peak blood concentration of the drug after administration;
[0392] AUC last Area under the blood drug concentration-time curve from zero to infinity;
[0393] AUC INF_obs Area under the blood drug concentration-time curve from zero to the final measurable concentration;
[0394] CI_90_Lower~Upper: Lower and upper limits of the 90% confidence interval;
[0395] The following conclusions can be drawn from the above data:
[0396] (1) The results of impurity content show:
[0397] Under fresh preparation conditions (0 days):
[0398] The tablets prepared in Example 1 (with added acidic excipients) contained 0.10% impurity D, undetectable impurity H, 0.01% of other single impurities, and 0.24% of total impurities, all of which were far below the impurity limits (Impurity D ≤ 0.98%, Impurity H ≤ 0.20%, Other maximum single impurities ≤ 0.20%, Total impurities ≤ 2.9%).
[0399] The tablets prepared in Example 5 (without acidic excipients) contained 0.09% impurity D, undetectable impurity H, 0.01% other maximum single impurity, and 0.24% total impurity. All of these contents were within the impurity limit standards (Impurity D ≤ 0.98%, Impurity H ≤ 0.20%, other maximum single impurity ≤ 0.20%, total impurity ≤ 2.9%), which were basically consistent with the impurity contents in Example 1 (with acidic excipients added).
[0400] Placed at 40℃ for 30 days:
[0401] The tablets prepared in Example 1 (with added acidic excipients) contained 0.09% impurity D, undetectable impurity H, a maximum single impurity content of 0.01%, and a total impurity content of 0.23%. Compared with tablets prepared under fresh conditions (0 days), the changes in each impurity were negligible and all were far below the impurity limits (impurity D content ≤ 0.98%, impurity H content ≤ 0.20%, other maximum single impurity content ≤ 0.20%, total impurity content ≤ 2.9%), demonstrating that the tablets exhibited good and significant stability.
[0402] The tablets prepared in Example 5 (omitting acidic excipients) contained 0.42% impurity D, 0.16% impurity H, 0.11% other maximum single impurity, and 0.84% total impurities. Compared to tablets prepared fresh (0 days), the impurity content of tablets prepared in Example 5 (omitting acidic excipients) after 30 days at 40°C showed a significant increase. Specifically, the impurity D content of tablets prepared in Example 5 (omitting acidic excipients) after 30 days at 40°C was approximately four times that of tablets prepared in Example 1 (with acidic excipients added) under the same conditions. Newly generated impurity H, other maximum single impurity, and total impurity all increased to varying degrees. The content of each impurity was higher than that of tablets prepared in Example 1 (with acidic excipients added), indicating poorer stability.
[0403] Placed for 30 days under high humidity (75%):
[0404] The tablets prepared in Example 1 (with added acidic excipients) contained 0.10% impurity D, undetectable impurity H, a maximum single impurity content of 0.01%, and a total impurity content of 0.24%. Compared with tablets prepared under fresh conditions (0 days), the content of each impurity did not increase and was far below the impurity limits (impurity D content ≤ 0.98%, impurity H content ≤ 0.20%, other maximum single impurity content ≤ 0.20%, total impurity content ≤ 2.9%), demonstrating good and significant tablet stability.
[0405] The tablets prepared in Example 5 (omitting acidic excipients) contained 0.35% impurity D, 0.20% impurity H, and a maximum single impurity content of 0.09%, with a total impurity content of 0.76%. Compared to tablets prepared fresh (0 days), the impurity content of tablets prepared in Example 5 (omitting acidic excipients) after 30 days of storage under high humidity (75%) conditions increased significantly. The content of all impurities was higher than that in Example 1 (with added acidic excipients), and the stability was worse than that in Example 1 (with added acidic excipients).
[0406] Placed under 4500±500 Lx light for 30 days:
[0407] The tablets prepared in Example 1 (with added acidic excipients) contained 0.08% impurity D, undetectable impurity H, a maximum single impurity content of 0.01%, and a total impurity content of 0.22%. Compared with tablets prepared under fresh conditions (0 days), the content of each impurity did not increase and was far below the impurity limits (impurity D content ≤ 0.98%, impurity H content ≤ 0.20%, other maximum single impurity content ≤ 0.20%, total impurity content ≤ 2.9%), demonstrating good and significant stability of the tablets.
[0408] The tablets prepared in Example 5 (omitting acidic excipients) contained 0.23% impurity D, 0.02% impurity H, and a maximum single impurity content of 0.06%, with a total impurity content of 0.68%. Compared to tablets prepared fresh (0 days), the tablets prepared in Example 5 (omitting acidic excipients) showed a significant increase in impurity content after 30 days of exposure to light at 4500±500 Lx. The content of all impurities was higher than that in Example 1 (with added acidic excipients), and the tablets exhibited poorer stability.
[0409] The above results indicate that the tablets prepared in Example 1 (with added acidic excipients) have higher stability than those prepared in Example 5 (without acidic excipients).
[0410] (2) The dissolution behavior results show that:
[0411] The formulation obtained in Example 1 (with added acidic excipients) completely disintegrated in 60 seconds with no accumulation at the bottom of the container, and the dissolution rate was 100%, which is far higher than the dissolution limit (≥85%), indicating good dissolution behavior.
[0412] The formulation of Example 5 (omitting acidic excipients) completely disintegrated within 5 minutes, with a significantly increased disintegration time (5 times that of Example 1). Approximately half of the container was filled at the bottom, and the dissolution rate was 65%, which did not meet the dissolution limit standard (≥85%). Due to the poor dissolution behavior, qualified tablets could not be obtained.
[0413] The above results indicate that the tablets prepared in Example 1 (with added acidic excipients) have a significant dissolution effect.
[0414] (3) The pH results of the microenvironment during tablet dissolution showed that:
[0415] The tablet intermediate prepared by adding acidic excipients to the component of Example 1 had a microenvironment pH of 4.02 during dissolution. The tablet intermediate prepared by omitting acidic excipients to the component of Example 5 had a microenvironment pH of 5.26 during dissolution. The addition of acidic excipients to the component of Example 1 lowered the microenvironment pH, making the active pharmaceutical ingredient more soluble and significantly improving the dissolution rate of the tablets, further supporting the accuracy of the above dissolution behavior results.
[0416] (4) Results of tablet weight difference show:
[0417] The tablet intermediate prepared by adding acidic excipients to the components of Example 1 has good particle flowability, more uniform filling weight, and small tablet weight difference, which is only -1.82% to 1.39%, significantly less than the limit standard ±7.5%.
[0418] The tablet intermediate prepared by omitting acidic excipients in Example 5 has good particle flowability, uniform filling weight, and small tablet weight variation, ranging from -1.76% to 1.54%, which is significantly less than the limit standard of ±7.5%.
[0419] (5) Bioequivalence results show that:
[0420] In Example 1, the 90% confidence intervals of the peak concentration (Cmax) on an empty stomach and after a meal, as well as the area under the plasma concentration-time curve (AUC), were both between 80% and 125%, which is equivalent to the reference formulation.
[0421] In summary, ① tablets prepared using the acidic excipients of this disclosure (e.g., in Example 1, with the addition of fumaric acid) exhibit good stability and dissolution behavior, and are bioequivalent to the reference formulation; ② tablets obtained by omitting the acidic excipients (e.g., in Example 5, without the addition of fumaric acid) have poor stability and dissolution behavior, and cannot yield qualified tablets.
[0422] V. The above results show that tablets prepared by adding acidic excipients have the best effect (Example 1). Therefore, the following results analysis, based on Example 1, explores the effect of changing the type of acidic excipient on tablet quality by changing the type of acidic excipient:
[0423] 1. The differences are shown in Table 37:
[0424] Table 37
[0425]
[0426] 2. Formulation comparisons are shown in Tables 38-41:
[0427] Table 38
[0428]
[0429] Table 39
[0430]
[0431] Table 40
[0432]
[0433] Table 41
[0434]
[0435] The following conclusions can be drawn from the above data:
[0436] (1) The results of impurity content show:
[0437] Under fresh preparation conditions (0 days):
[0438] The impurity D contents of Example 1 (acidic excipient = fumaric acid), Example 6 Method 1 (acidic excipient = tartaric acid), Example 6 Method 2 (acidic excipient = citric acid), Example 6 Method 3 (acidic excipient = lactic acid), and Example 6 Method 4 (acidic excipient = acetic acid) were 0.10%, 0.08%, 0.09%, 0.10%, and 0.10%, respectively, which are far below the limit standard (≤0.98%). The impurity H contents were all undetectable, far below the limit standard (≤0.20%). The maximum single impurity content was 0.01%, far below the limit standard (≤0.20%). The total impurity content was 0.24%, 0.21%, 0.23%, 0.26%, and 0.19%, far below the limit standard (≤2.9%), indicating good stability.
[0439] Placed at 40℃ for 30 days:
[0440] The impurity D content of Example 1 (acidic excipient = fumaric acid) was 0.09%, which is far below the limit standard (≤0.98%); the impurity H content was undetectable, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); the total impurity content was 0.23%, which is far below the limit standard (≤2.9%), and the stability was good.
[0441] The impurity D contents of Method 1 (acidic excipient = tartaric acid), Method 2 (acidic excipient = citric acid), Method 3 (acidic excipient = lactic acid), and Method 4 (acidic excipient = acetic acid) in Examples 6 were 0.16%, 0.21%, 0.17%, and 0.19%, respectively, which are far below the limit standard (≤0.98%); the impurity H contents were 0.05%, 0.10%, 0.12%, and 0.10%, respectively, which are far below the limit standard (≤0.20%); the maximum contents of other single impurities were 0.05%, 0.11%, 0.11%, and 0.10%, respectively, which are far below the limit standard (≤0.20%); and the total impurity contents were 0.46%, 0.52%, 0.57%, and 0.47%, respectively, which are far below the limit standard (≤2.9%), indicating good stability.
[0442] Placed for 30 days under high humidity (75%):
[0443] The impurity D content of Example 1 (acidic excipient = fumaric acid) was 0.10%, which is far below the limit standard (≤0.98%); the impurity H content was undetectable, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); the total impurity content was 0.24%, which is far below the limit standard (≤2.9%), and the stability was good.
[0444] The impurity D contents of Method 1 (acidic excipient = tartaric acid), Method 2 (acidic excipient = citric acid), and Method 4 (acidic excipient = acetic acid) in Example 6 were 0.13%, 0.19%, and 0.18%, respectively, which are far below the limit standard (≤0.98%); the impurity H contents were 0.08%, 0.04%, and 0.11%, respectively, which are far below the limit standard (≤0.20%); the maximum contents of other single impurities were 0.07%, 0.12%, and 0.12%, respectively, which are far below the limit standard (≤0.20%); and the total impurity contents were 0.39%, 0.43%, and 0.42%, respectively, which are far below the limit standard (≤2.9%), indicating good stability.
[0445] In Example 6, Method 3 (acidic excipient = lactic acid), the impurity D content was 0.19%, far below the limit standard (≤0.98%); the impurity H content was 0.14%, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.12%, far below the limit standard (≤0.20%); and the total impurity content was 0.60%, far below the limit standard (≤2.9%). The stability was slightly worse than that of Example 1.
[0446] Placed under 4500±500 Lx light for 30 days:
[0447] The impurity D content of Example 1 (acidic excipient = fumaric acid) was 0.08%, which is far below the limit standard (≤0.98%); the impurity H content was undetectable, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); the total impurity content was 0.22%, which is far below the limit standard (≤2.9%), and the stability was good.
[0448] The impurity D contents of Method 1 (acidic excipient = tartaric acid), Method 2 (acidic excipient = citric acid), and Method 4 (acidic excipient = acetic acid) in Example 6 were 0.10%, 0.15%, and 0.12%, respectively, which are far below the limit standard (≤0.98%); the impurity H contents were 0.05%, 0.09%, and 0.08%, respectively, which are far below the limit standard (≤0.20%); the maximum contents of other single impurities were 0.05%, 0.10%, and 0.10%, respectively, which are far below the limit standard (≤0.20%); and the total impurity contents were 0.40%, 0.41%, and 0.34%, respectively, which are far below the limit standard (≤2.9%), indicating good stability.
[0449] In Example 6, Method 3 (acidic excipient = lactic acid), the impurity D content was 0.14%, far below the limit standard (≤0.98%); the impurity H content was 0.16%, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.10%, far below the limit standard (≤0.20%); and the total impurity content was 0.54%, far below the limit standard (≤2.9%). The stability was slightly worse than that of Example 1.
[0450] The above results indicate that the tablets prepared by methods 1-4 in Examples 1 and 6 all meet the standard requirements in terms of quality, and their stability was also in compliance with the quality standards during the stability test. The tablets prepared by methods 1 (acidic excipient = fumaric acid), method 1 (acidic excipient = tartaric acid), method 2 (acidic excipient = citric acid), and method 4 (acidic excipient = acetic acid) in Example 6 have better stability than those prepared by method 3 (acidic excipient = lactic acid) in Example 6.
[0451] (2) The dissolution behavior results show that:
[0452] The formulation obtained in Example 1 (acidic excipient = fumaric acid) completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the container. The dissolution rate was 100%, which is far above the dissolution limit (≥85%), and the dissolution behavior was good and significant.
[0453] The formulations obtained by Method 1 (acidic excipient = tartaric acid) in Example 6 and Method 2 (acidic excipient = citric acid) in Example 6 completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the container. The dissolution rates were 95% and 92%, respectively, which are far above the dissolution limit (≥85%), indicating good dissolution behavior.
[0454] Although the formulations obtained by Method 3 (acidic excipient = lactic acid) and Method 4 (acidic excipient = acetic acid) in Example 6 completely disintegrated in 60s, 1 / 3 and 1 / 4 of the volume of the container were accumulated at the bottom of the container, respectively. The dissolution rate was reduced to 72% and 80%, which did not meet the dissolution limit standard (≥85%). The dissolution behavior was poor, and it was impossible to prepare tablet products with qualified dissolution behavior.
[0455] The above results indicate that the tablets prepared by Example 1 (acidic excipient = fumaric acid), Method 1 of Example 6 (acidic excipient = tartaric acid), and Method 2 of Example 6 (acidic excipient = citric acid) exhibit significantly better dissolution behavior than those prepared by Method 3 of Example 6 (acidic excipient = lactic acid) and Method 4 of Example 6 (acidic excipient = acetic acid). Furthermore, Method 3 of Example 6 (acidic excipient = lactic acid) and Method 4 of Example 6 (acidic excipient = acetic acid) cannot prepare tablet products with satisfactory dissolution behavior.
[0456] (3) The pH results of the microenvironment during tablet dissolution showed that:
[0457] The tablet intermediate of Example 1 (acidic excipient = fumaric acid) had a microenvironment pH of 4.02 during dissolution. The microenvironment pH of Method 1 (acidic excipient = tartaric acid) and Method 2 (acidic excipient = citric acid) in Example 6 were 4.18 and 4.35, respectively. The acidic microenvironment conditions facilitated the dissolution of the active pharmaceutical ingredient, thereby significantly improving the tablet's dissolution rate and maintaining good stability.
[0458] However, the microenvironmental pH of Method 3 (acidic excipient = lactic acid) and Method 4 (acidic excipient = acetic acid) in Example 6 were 5.56 and 5.12, respectively; the pH was significantly higher than that of Example 1 (acidic excipient = fumaric acid), which prevented the active pharmaceutical ingredient from dissolving sufficiently, thus reducing the dissolution rate. Simultaneously, because lactic acid is less stable than the acidic excipients (fumaric acid, tartaric acid, citric acid, acetic acid) used in this application, it degraded, leading to an increase in the impurity content of related substances and reducing the stability of the tablets. This further verified the accuracy of the above-mentioned 1) impurity content results and 2) dissolution behavior results.
[0459] (4) Results of tablet weight difference show:
[0460] The tablet intermediate prepared in Example 1 (acidic excipient = fumaric acid) has good particle flowability, more uniform filling weight, and a small tablet weight difference of -1.82% to 1.39%, which is significantly less than the limit standard of ±7.5%.
[0461] The tablet weight differences obtained from Method 1 (acidic excipient = tartaric acid), Method 2 (acidic excipient = citric acid), Method 3 (acidic excipient = lactic acid), and Method 4 (acidic excipient = acetic acid) in Example 6 were -2.78% to 2.39%, -1.98% to 2.56%, -2.82% to 3.39%, and -2.75% to 3.04%, respectively, all significantly less than the limit standard ±7.5%.
[0462] The above results indicate that the tablet weight differences prepared by Example 1 (acidic excipient = fumaric acid), Method 1 of Example 6 (acidic excipient = tartaric acid), Method 2 of Example 6 (acidic excipient = citric acid), Method 3 of Example 6 (acidic excipient = lactic acid), and Method 4 of Example 6 (acidic excipient = acetic acid) all meet the limit standards.
[0463] In summary, ① tablets with good stability and dissolution behavior can be prepared using the acidic excipients disclosed herein (e.g., citric acid, fumaric acid, tartaric acid); ② when fumaric acid is used as the acidic excipient, the prepared tablets (e.g., Example 1) exhibit the best stability and dissolution behavior; ③ conversely, tablets obtained using acidic fillers other than those disclosed herein (e.g., lactic acid in Method 3 of Example 6 and acetic acid in Method 4 of Example 6) have poor stability and dissolution behavior, and qualified tablets cannot be obtained.
[0464] VI. Results Analysis II. This study investigated the effect of different types of acidic excipients on tablet quality. The following section explores the effect of varying amounts of fumaric acid in the tablet core material on tablet quality by changing the dosage of the acidic excipient fumaric acid:
[0465] 1. The differences are shown in Table 42:
[0466] Table 42
[0467]
[0468] 2. Formulation comparisons are shown in Tables 43-47:
[0469] Table 43
[0470]
[0471]
[0472] Table 44
[0473]
[0474] Table 45
[0475]
[0476] Table 46
[0477]
[0478] Table 47
[0479]
[0480]
[0481] The following conclusions can be drawn from the above data:
[0482] (1) The results of impurity content show:
[0483] Under fresh preparation conditions (0 days):
[0484] The impurity D content in Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), Example 7 Method 4 (fumaric acid = 0.50 wt%), and Comparative Example 2 (fumaric acid = 2.50 wt%) was 0.08–0.10%, far below the limit standard (≤0.98%); the impurity H content was undetectable in all cases, far below the limit standard (≤0.20%); the maximum single impurity content was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.21–0.24%, far below the limit standard (≤2.9%).
[0485] Placed at 40℃ for 30 days:
[0486] The impurity D content of Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), Example 7 Method 4 (fumaric acid = 0.50 wt%), and Comparative Example 2 (fumaric acid = 2.50 wt%) was 0.08–0.09%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum single impurity content was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.21–0.24%, far below the limit standard (≤2.9%), and the stability was good.
[0487] Placed for 30 days under high humidity (75%):
[0488] The impurity D content of Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), Example 7 Method 4 (fumaric acid = 0.50 wt%), and Comparative Example 2 (fumaric acid = 2.50 wt%) was 0.08–0.10%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum single impurity content was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.22–0.24%, far below the limit standard (≤2.9%), and the stability was good.
[0489] Placed under 4500±500 Lx light for 30 days:
[0490] The impurity D content in Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), Example 7 Method 4 (fumaric acid = 0.50 wt%), and Comparative Example 2 (fumaric acid = 2.50 wt%) was 0.08%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum single impurity content was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.22%–0.25%, far below the limit standard (≤2.9%), indicating good stability.
[0491] The above results indicate that the amount of fumaric acid used in this disclosure can be used to prepare tablet products with acceptable stability.
[0492] (2) The dissolution behavior results show that:
[0493] The formulations obtained in Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), Example 7 Method 4 (fumaric acid = 0.50 wt%), and Comparative Example 2 (fumaric acid = 2.50 wt%) all completely disintegrated within 60 seconds, with a small amount of buildup at the bottom of the container. The dissolution rate was 91-100%, which is far above the dissolution limit (≥85%), indicating good and significant dissolution behavior.
[0494] The above results indicate that the amount of fumaric acid used in this disclosure can be sufficient to prepare tablet products with acceptable dissolution behavior.
[0495] (3) The pH results of the microenvironment during tablet dissolution showed that:
[0496] The microenvironment pH values for Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), and Example 7 Method 4 (fumaric acid = 0.50 wt%) were 4.02, 4.09, 4.03, 4.00, and 3.96, respectively. The acidic microenvironment pH condition made the active pharmaceutical ingredient more soluble, thereby significantly improving the dissolution rate of the tablets and maintaining good stability.
[0497] The microenvironment pH of Comparative Example 2 (fumaric acid = 2.50 wt%) was 3.05, which was significantly different from that of the reference preparation (microenvironment pH 4.01).
[0498] (4) Results of tablet weight difference show:
[0499] The tablet intermediates prepared in Example 1 (fumaric acid = 0.10 wt%), Example 7 Method 1 (fumaric acid = 0.05 wt%), Example 7 Method 2 (fumaric acid = 0.15 wt%), Example 7 Method 3 (fumaric acid = 0.20 wt%), Example 7 Method 4 (fumaric acid = 0.50 wt%), and Comparative Example 2 (fumaric acid = 2.50 wt%) showed good particle flowability, more uniform tablet weight, and small tablet weight variation, all significantly less than the limit standard ±7.5%.
[0500] (5) The dissolution curve results show:
[0501] The tablets prepared in Example 1 (fumaric acid = 0.10% by weight) showed dissolution rates of 71%, 90%, and 96% at 5 min, 10 min, and 15 min, respectively, under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, and rotation speed: 50 rpm. These results were essentially consistent with the reference formulation (dissolution rates of 73%, 91%, and 97% at 5 min, 10 min, and 15 min, respectively). The dissolution rate at 15 min was greater than 85%, indicating extremely rapid dissolution.
[0502] The tablets prepared by Method 1 (fumaric acid = 0.05 wt%), Method 2 (fumaric acid = 0.15 wt%), Method 3 (fumaric acid = 0.20 wt%), and Method 4 (fumaric acid = 0.50 wt%) in Example 7 showed essentially the same dissolution rate at each time point compared to the reference formulation and Example 1, all under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, and rotation speed: 50 rpm, which are all extremely rapid dissolution.
[0503] The tablets prepared in Comparative Example 2 (fumaric acid = 2.50 wt%), under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, rotation speed: 50 rpm, compared with the reference preparation and Example 1, had a dissolution rate of only 56% at 5 min, which was 17% slower than the reference preparation (73% dissolution at 5 min); the dissolution rate at 10 min was 78%, which was 13% slower than the reference preparation (91% dissolution at 10 min); it was significantly slower than Example 1, and the dissolution rates at 5 min and 10 min were inconsistent with the dissolution rate of the reference preparation.
[0504] In summary, ① tablets with good stability and dissolution behavior can be prepared using the acidic excipient dosage of this disclosure (e.g., fumaric acid dosage = 0.05-0.50% by weight); ② conversely, tablets with a microenvironment pH that differs greatly from the reference formulation when using acidic excipient dosages other than those disclosed in this disclosure (e.g., Comparative Example 2, fumaric acid dosage = 2.5%), and dissolution in pH 4.5 acetate buffer at 5 min and 10 min is slower than that of the reference formulation, making it impossible to obtain qualified tablets.
[0505] Example 1 of this disclosure was compared with the formulations in patents CN115364065A, CN111973565A, and CN118078767A. The formulation in patent CN115364065A was used as Comparative Example 1, the formulation in patent CN111973565A as Comparative Example 2, and patent CN118078767A as Comparative Example 3. Tablets were prepared and compared, and the results are as follows:
[0506] VII. The formula in patent CN115364065A was used as comparative example 1.
[0507] 1. Formulation comparisons are shown in Tables 48-51:
[0508] Table 48
[0509]
[0510] Table 49
[0511]
[0512] Table 50
[0513]
[0514] Table 51
[0515]
[0516]
[0517] The following conclusions can be drawn from the above data:
[0518] (1) The results of impurity content show:
[0519] Under fresh preparation conditions (0 days):
[0520] The impurity D content in Example 1 and Comparative Example 1 was 0.10% and 0.11%, respectively, which are far below the limit standard (≤0.98%); the impurity H content was undetectable in both cases, which are far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which are far below the limit standard (≤0.20%); and the total impurity content was 0.24% and 0.22%, respectively, which are far below the limit standard (≤2.9%).
[0521] Placed at 40℃ for 30 days:
[0522] In Example 1, the impurity D content was 0.09%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); and the total impurity content was 0.23%, far below the limit standard (≤2.9%), indicating good stability.
[0523] The content of impurity D in Comparative Example 1 was 1.26%, exceeding the limit standard (≤0.98%); the content of impurity H was 0.28%, exceeding the limit standard (≤0.20%); the maximum content of other single impurities was 0.35%, exceeding the limit standard (≤0.20%); and the total impurity content was 1.79%, below the limit standard (≤2.9%).
[0524] Placed for 30 days under high humidity (75%):
[0525] The impurity D content in Example 1 was 0.10%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.24%, far below the limit standard (≤2.9%), and the stability was good.
[0526] The content of impurity D in Comparative Example 1 was 1.17%, exceeding the limit standard (≤0.98%); the content of impurity H was 0.22%, exceeding the limit standard (≤0.20%); the maximum content of other single impurities was 0.21%, exceeding the limit standard (≤0.20%); and the total impurity content was 1.69%, below the limit standard (≤2.9%).
[0527] Placed under 4500±500 Lx light for 30 days:
[0528] The impurity D content in Example 1 was 0.08%, far below the limit standard (≤0.98%); the impurity H content was undetectable, far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, far below the limit standard (≤0.20%); the total impurity content was 0.22%, far below the limit standard (≤2.9%), and the stability was good.
[0529] The content of impurity D in Comparative Example 1 was 1.12%, exceeding the limit standard (≤0.98%); the content of impurity H was 0.21%, exceeding the limit standard (≤0.20%); the maximum content of other single impurities was 0.20%, below the limit standard (≤0.20%); and the total impurity content was 1.65%, below the limit standard (≤2.9%).
[0530] The above results indicate that Example 1 yields a tablet product with good stability. Comparative Example 1, however, had impurity levels exceeding the limit standards, making it impossible to obtain qualified tablets.
[0531] (2) The dissolution behavior results show that:
[0532] The formulation obtained in Example 1 completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the cup, and the dissolution rate was 100%, which is far above the dissolution limit (≥85%), indicating good and significant dissolution behavior.
[0533] The formulation obtained in Comparative Example 1 completely disintegrated in 60 seconds, with a small amount of buildup at the bottom of the cup. The dissolution rate was 76%, which was below the dissolution limit (≥85%), and therefore qualified tablets could not be obtained.
[0534] (3) Results of tablet weight difference show:
[0535] The tablets prepared in Example 1 have good compressibility, more uniform filling weight, and small tablet weight difference, ranging from -1.82% to 1.39%, which is significantly less than the limit standard of ±7.5%.
[0536] The tablets prepared in Comparative Example 1 had a tablet weight variation controlled within -2.42% to 3.11%, which was significantly less than the limit standard of ±7.5%.
[0537] (4) The dissolution curve results show:
[0538] The tablets prepared in Example 1, under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, rotation speed: 50 rpm, showed a dissolution trend basically consistent with the reference formulation, with a dissolution rate of more than 85% after 15 min, which is considered extremely rapid dissolution.
[0539] The tablets prepared in Comparative Example 1, under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, rotation speed: 50 rpm, had a dissolution rate of only 74% at 15 min compared with the reference preparation and Example 1, which did not meet the requirement of a dissolution rate greater than 85% at 15 min. This was significantly slower than Example 1 and inconsistent with the dissolution of the reference preparation, making it impossible to obtain a qualified product.
[0540] (5) The results of the mixing uniformity show that:
[0541] The tablet intermediate prepared in Example 1 had a mixing homogeneity RSD of 1.2%, which is far below the limit standard (≤5.0%).
[0542] The tablet intermediate prepared in Comparative Example 1 had a mixing homogeneity RSD value of 6.0%, which exceeded the limit standard (≤5.0%), and therefore could not be used to obtain a qualified product.
[0543] In summary, ① tablets with good stability, uniformity, and dissolution behavior can be prepared using the formulation disclosed herein (such as Example 1); ② conversely, tablets obtained using formulations other than those disclosed herein (such as Comparative Example 1) have poor stability, impurity content exceeding the limit standard, poor dissolution behavior, poor mixing uniformity of tablet intermediates, and cannot obtain qualified tablets.
[0544] 8. The formula in patent CN111973565A was used as comparative example 2.
[0545] 1. The main differences are shown in Table 52:
[0546] Table 52
[0547] Example Acidic excipient - Fumaric acid (mass percentage / tablet) Filler - Mannitol Example 1 0.22mg Crystal form β, particle size D90 = 142 μm Comparative Example 2 5.5mg Model SD200
[0548] 2. Formulation comparisons are shown in Tables 53-57:
[0549] Table 53
[0550]
[0551] Table 54
[0552]
[0553] Table 55
[0554] sample intermediate pH Reference formulation 4.01 Example 1 4.02 Comparative Example 2 3.05
[0555] Table 56
[0556]
[0557] Table 57
[0558] Sample / Cumulative Dissolution % 5min 10min 15min 30min 45min 60min Reference formulation 73 91 97 100 100 101 Example 1 71 90 96 99 100 100 Comparative Example 2 56 78 91 92 97 97
[0559] The following conclusions can be drawn from the above data:
[0560] (1) The results of impurity content show:
[0561] Under fresh preparation conditions (0 days):
[0562] The impurity D content of Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) was 0.10% and 0.09%, respectively, which are far below the limit standard (≤0.98%); the impurity H content was not detected in either case, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.24% and 0.21%, respectively, which are far below the limit standard (≤2.9%).
[0563] Placed at 40℃ for 30 days:
[0564] The impurity D content of Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) was 0.09%, which is far below the limit standard (≤0.98%); the impurity H content was not detected in either example, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.23% and 0.24%, respectively, which is far below the limit standard (≤2.9%).
[0565] Placed for 30 days under high humidity (75%):
[0566] The impurity D content of Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) was 0.10% and 0.09%, respectively, which are far below the limit standard (≤0.98%); the impurity H content was not detected in either case, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.24% and 0.22%, respectively, which are far below the limit standard (≤2.9%).
[0567] Placed under 4500±500 Lx light for 30 days:
[0568] The impurity D content of Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) was 0.08%, which is far below the limit standard (≤0.98%); the impurity H content was not detected in either case, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.22% and 0.25%, respectively, which is far below the limit standard (≤2.9%).
[0569] (2) The dissolution behavior results show that:
[0570] The formulations obtained in Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) completely disintegrated within 60 seconds, with a small amount of buildup at the bottom of the container. The dissolution rates were 100% and 91%, respectively, which were far above the dissolution limit (≥85%), indicating good and significant dissolution behavior.
[0571] (3) The pH results of the microenvironment during tablet dissolution showed that:
[0572] The microenvironment pH of Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) were 4.02 and 3.05, respectively; the microenvironment pH of the reference preparation was 4.01. Example 1 (fumaric acid = 0.22 mg / tablet) was basically consistent with the reference preparation, while Comparative Example 2 (fumaric acid = 5.5 mg / tablet) differed significantly from the reference preparation.
[0573] (4) Results of tablet weight difference show:
[0574] The tablet intermediates prepared in Example 1 (fumaric acid = 0.22 mg / tablet) and Comparative Example 2 (fumaric acid = 5.5 mg / tablet) showed good particle flowability, more uniform tablet weight, and small tablet weight variation, ranging from -1.82% to 1.39% and -2.78% to 1.97%, respectively, both significantly less than the limit standard ±7.5%.
[0575] (5) The dissolution curve results show:
[0576] The tablets prepared in Example 1 showed essentially the same dissolution rate as the reference formulation under the following conditions: dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, rotation speed: 50 rpm. The dissolution rate was greater than 85% after 15 min, which is considered extremely rapid dissolution.
[0577] The tablets prepared in Comparative Example 2, under the conditions of dissolution medium: pH 4.5 acetate buffer, medium volume: 900 ml, rotation speed: 50 rpm, compared with the reference preparation and Example 1, had a dissolution rate of only 56% at 5 min, which was 17% slower than the reference preparation (73% dissolution at 5 min); the dissolution rate at 10 min was 78%, which was 13% slower than the reference preparation (91% dissolution at 10 min); it was significantly slower than Example 1, and the dissolution rates at 5 min and 10 min were inconsistent with the dissolution rate of the reference preparation.
[0578] In summary, ① using the acidic excipient dosage of this disclosure (e.g., in Example 1, fumaric acid dosage = 0.22 mg / tablet) can prepare tablets with good stability and dissolution behavior; ② conversely, using acidic excipient dosages other than those disclosed in this disclosure (e.g., in Comparative Example 2, fumaric acid dosage = 5.5 mg / tablet) results in tablets with a significantly different microenvironment pH compared to the reference formulation. Furthermore, in pH 4.5 acetate buffer, the dissolution rate is only 56% at 5 min, 17% slower than the reference formulation (73% dissolution at 5 min); the dissolution rate at 10 min is 78%, 13% slower than the reference formulation (91% dissolution at 10 min), showing inconsistency with the reference formulation's dissolution, thus failing to yield qualified tablets.
[0579] 9. The formula in patent CN118078767A was used as comparative example 3.
[0580] 1. The main differences are shown in Table 58:
[0581] Table 58
[0582]
[0583] 2. Formulation comparisons are shown in Figure 59.
[0584] Table 59
[0585]
[0586]
[0587] The following conclusions can be drawn from the above data:
[0588] (1) The results of impurity content show:
[0589] Under fresh preparation conditions (0 days):
[0590] The impurity D contents of Example 1 (mannitol β crystal form), Comparative Example 3 Method 1 (mannitol β crystal form), and Comparative Example 3 Method 2 (mixture of mannitol α and β crystal forms) were 0.10%, 0.08%, and 0.10%, respectively, which are far below the limit standard (≤0.98%); the impurity H contents were not detected in all cases, which are far below the limit standard (≤0.20%); the maximum single impurity content was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity contents were 0.24%, 0.20%, and 0.24%, respectively, which are far below the limit standard (≤2.9%).
[0591] Placed at 40℃ for 30 days:
[0592] The impurity D content of Example 1 (mannitol β crystal form) was 0.09%, which is far below the limit standard (≤0.98%); the impurity H content was undetectable, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.23%, which is far below the limit standard (≤2.9%).
[0593] The impurity D contents of Comparative Example 3 Method 1 (mannitol β crystal form) and Comparative Example 3 Method 2 (mixture of mannitol α and β crystal forms) were 1.34% and 1.41%, respectively, exceeding the limit standard (≤0.98%); the impurity H contents were 0.30% and 0.35%, respectively, exceeding the limit standard (≤0.20%); the contents of other maximum single impurities were 0.31% and 0.28%, respectively, exceeding the limit standard (≤0.20%); and the total impurity contents were 1.97% and 2.10%, respectively, below the limit standard (≤2.9%).
[0594] Placed for 30 days under high humidity (75%):
[0595] The impurity D content of Example 1 (mannitol β crystal form) was 0.10% and 0.09%, respectively, which are far below the limit standard (≤0.98%); the impurity H content was undetectable, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.24%, which is far below the limit standard (≤2.9%).
[0596] The impurity D contents of Comparative Example 3 Method 1 (mannitol β crystal form) and Comparative Example 3 Method 2 (mixture of mannitol α and β crystal forms) were 1.28% and 1.36%, respectively, exceeding the limit standard (≤0.98%); the impurity H contents were 0.24% and 0.30%, respectively, exceeding the limit standard (≤0.20%); the maximum contents of other single impurities were 0.25% and 0.26%, respectively, exceeding the limit standard (≤0.20%); and the total impurity contents were 1.80% and 1.98%, respectively, below the limit standard (≤2.9%).
[0597] Placed under 4500±500 Lx light for 30 days:
[0598] The impurity D content of Example 1 (mannitol β crystal form) was 0.08%, which is far below the limit standard (≤0.98%); the impurity H content was undetectable, which is far below the limit standard (≤0.20%); the maximum content of other single impurities was 0.01%, which is far below the limit standard (≤0.20%); and the total impurity content was 0.22%, which is far below the limit standard (≤2.9%).
[0599] The impurity D contents of Comparative Example 3 Method 1 (mannitol β crystal form) and Comparative Example 3 Method 2 (mixture of mannitol α and β crystal forms) were 1.30% and 1.29%, respectively, exceeding the limit standard (≤0.98%); the impurity H contents were 0.21% and 0.27%, respectively, exceeding the limit standard (≤0.20%); the maximum contents of other single impurities were 0.20% and 0.21%, respectively, exceeding the limit standard (≤0.20%); and the total impurity contents were 1.74% and 1.82%, respectively, below the limit standard (≤2.9%).
[0600] In summary, ① stable tablets can be prepared using the mannitol crystal form disclosed herein (e.g., mannitol β crystal form in Example 1); ② conversely, tablets obtained using mannitol crystal forms other than those disclosed herein (e.g., a mixture of mannitol α and β crystal forms in Comparative Example 3) have poor stability, and some impurities exceed the limit standards during storage under different conditions, making it impossible to obtain qualified tablets.
[0601] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0602] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0603] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A vonoprazan fumarate tablet, characterized in that, The tablets include a tablet core and a coating covering the outer surface of the tablet core; Based on the total weight of the core, the raw materials of the core are: 12.15% by weight of vonoprazan fumarate, 70.16% by weight of β-mannitol, 10.00% by weight of microcrystalline cellulose, 0.10% by weight of fumaric acid, 5.00% by weight of croscarmellose sodium, 1.50% by weight of magnesium stearate and 1.09% by weight of hydroxypropyl cellulose; The particle size of the vonoprazan fumarate meets the following requirements: D90 is 25 μm, D50 is 12 μm, and D10 is 7 μm. The particle size of the β-crystalline mannitol meets the following requirements: D90 is 142 μm, D50 is 63 μm, and D10 is 25 μm. The coating is a gastrointestinal film-coating premix; based on the total weight of the tablets, the coating content is 6.0% by weight. When the β-crystalline mannitol was characterized by XRD, it exhibited characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
2. The method for preparing the tablet according to claim 1, characterized in that, The method includes the following steps: S1. β-crystalline mannitol, microcrystalline cellulose, sodium carboxymethyl cellulose (CMC) I, and vonoprazan fumarate I are mixed and treated to obtain a premixed material; S2. Add the premixed material to a high-speed wet granulator, and spray the mixture of fumaric acid solution and hydroxypropyl cellulose solution into the high-speed wet granulator for granulation, and collect 20-30 mesh particles by sieving. S3. After the particles are mixed with the second crosslinked sodium carboxymethyl cellulose and magnesium stearate, the resulting mixture is then subjected to tableting and coating processes in sequence. The particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm. The particle size of the β-crystalline mannitol meets the following requirements: D90 is 142 μm, D50 is 63 μm, and D10 is 25 μm. Based on the total weight of the tablet core, the raw materials of the tablet core include: 12.15% by weight of vonoprazan fumarate, 70.16% by weight of β-mannitol, 10.00% by weight of microcrystalline cellulose, 0.10% by weight of fumaric acid, 5.00% by weight of croscarmellose sodium, 1.50% by weight of magnesium stearate and 1.09% by weight of hydroxypropyl cellulose; In step S1, based on the total weight of the core, the content of the first cross-linked sodium carboxymethyl cellulose is 1% by weight. In step S3, based on the total weight of the core, the content of the second crosslinked sodium carboxymethyl cellulose is 4% by weight. When the β-crystalline mannitol was characterized by XRD, it exhibited characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
3. The method according to claim 2, characterized in that, The conditions for the first mixing process include: a rotation speed of 100-150 rpm and a time of 5-10 min.
4. The method according to claim 2, characterized in that, In step S2, the granulation conditions include: an inlet air temperature of 55~65℃, an injection velocity of the mixed liquid of 200~300 rpm, and an air volume of 15~20 m³ / h. 3 / h.
5. The method according to claim 2, characterized in that, The conditions for the second mixing process include: a rotation speed of 10-15 rpm and a time of 15-30 min.
6. A method for reducing the impurity content in the tablet of claim 1, characterized in that, The method includes the following steps: S1. β-crystalline mannitol, microcrystalline cellulose, sodium carboxymethyl cellulose (CMC) I, and vonoprazan fumarate I are mixed and treated to obtain a premixed material; S2. Add the premixed material to a high-speed wet granulator, and spray the mixture of fumaric acid solution and hydroxypropyl cellulose solution into the high-speed wet granulator for granulation, and collect 20-30 mesh particles by sieving. S3. After the particles are mixed with the second crosslinked sodium carboxymethyl cellulose and magnesium stearate, the resulting mixture is then subjected to tableting and coating processes in sequence. The particle size of the vonoprazan fumarate satisfies D90 of 25 μm, D50 of 12 μm, and D10 of 7 μm. The particle size of the β-crystalline mannitol satisfies D90 of 142 μm, D50 of 63 μm, and D10 of 25 μm. The impurities include impurity D and / or impurity H; impurity D is N-{[5-(2-fluorophenyl)-1-(pyridin-3-yl-sulfonyl)-1H-pyrrolo-3-yl]-methyl}-N-methylaspartic acid, and impurity H is 1-(5-(2-fluorophenyl)-1H-pyrrolo-3-yl)-N-methylmethylamine; When the β-crystalline mannitol was characterized by XRD, it exhibited characteristic peaks at diffraction angles 2θ of 10.468°, 11.430°, 14.627°, 16.799°, 21.685°, 25.919°, 26.610°, 28.177°, 31.750°, 32.663°, 33.602°, 38.707°, and 44.098°.
7. Use of the tablet of claim 1 or the tablet prepared by the method of any one of claims 2 to 6 in the preparation of a medicament for treating reflux esophagitis.
8. The use according to claim 7, characterized in that, The tablets exhibit a dissolution rate of ≥85% within 30 minutes under the specified dissolution conditions. The dissolution conditions include: using 900 mL of acetate buffer solution at pH 4.5 as the dissolution medium and rotating at 50 rpm.
Citation Information
Patent Citations
Vonoprazan fumarate pharmaceutical composition
CN107224438A
Vonoprazan fumarate-containing tablet and determination method for dissolution rate thereof
CN111973565A
Tablet containing Vonoprasone fumarate
CN118078767A
